Climate and soil properties drive microplastic enrichment patterns in agricultural soils across a multi-country survey - Martine Graf; Michaela K. Reay; Yingming Sun; Fan Ding; Siyang Ren; Kai Wang; Changrong Yan; Shitong Li; Tida Ge; Xuejun Liu; Ruimin Qi; Jixiao Cui; et al. (Environmental Pollution, 2026)

Bioinspired pullulan-based adhesive coacervate films for targeted buccal delivery of peptides - Margarida M.A. Sacramento; Nazanin Z. Ezazi; Eleftheria Pantazoglou; Philip Mark Lund; Marco van de Weert; Zhongyang Zhang; Rui Vitorino; Floriane Bahuon; Ragna Berthelsen; Stephen T. Buckley; Gavrielle R. Untracht; Peter Eskil Andersen; et al. (Carbohydrate Polymers, 2026)

On the efficiency of biosphere–Atmosphere ammonia exchange processes over a Scots pine forests and its link to ecosystem activity - E.A. Melman; P. Wintjen; J. Zhang; S. Rutledge-Jonker; A. Hensen; K. Felter; M.K. van der Molen; H. Snellen; J. de Boer; M. Eijkelboom; M. Haaima; R. van der Hoff; et al. (Agricultural and Forest Meteorology, 2026)

Leptomyxa echinata n. sp. – a remarkable species of the genus Leptomyxa (Amoebozoa: Tubulinea) from the sediment of an artificial freshwater pond - Nikita S. Kulishkin; Elizaveta D. Chikadze; Elena S. Nassonova; Andrey N. Tsyganov; Natalia G. Mazei; R. Wang; Yuanyuan Xue; M. Rooman; Wenjing Zhang; Yuri A. Mazei; Jun Yang; Alexey V. Smirnov (European Journal of Protistology, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Discriminating skarn deposits with epidote chemistry: a case study of Dolphin Tungsten (W) Skarn, King Island, Tasmania - Angela I. S. Costa; David R. Cooke; Yamila Cajal; Lejun Zhang; Charlys V. S. Neves; Henry Schaumburg; Jack Ward; Jeffrey Oalmann; Ivan Belousov; Michael J. Baker (Mineralium Deposita, 2026)
This study evaluates epidote chemistry as a discriminator of and vector to skarn mineralization, based on LA-ICP-MS analyses of epidote from the Devonian Dolphin Tungsten (W) skarn and Neoproterozoic mafic volcanic rocks (up to 6.5 km northeast from the deposit) on King Island, Tasmania. Epidote from the mafic volcanics has distinctive compositions relative to skarn epidote and metamorphic signatures and records a distal footprint of magmatic-hydrothermal fluids > 4.5 km from Dolphin. Exoskarn epidote, replacing garnet during retrograde alteration, has low Fe/Al ratios (< 0.5) and high Sn (mean > 100 ppm) and Bi (mean > 10 ppm). Endoskarn epidote, replaced feldspar phenocrysts and/or occurs in veins, and is enriched in B, Li, As and Sb (mean > 5 ppm). U-Pb dating of exoskarn epidote yielded a 356.7 ± 8.9 Ma age, which is within uncertainty of the Sandblow Granodiorite (~ 351 Ma), whereas the City of Melbourne Bay Volcanics epidote yielded a 394 ± 65 Ma age consistent with the emplacement of the Tabberabberan‑orogeny intrusions in western Tasmania. A comparative analysis, involving a compilation of 6,008 analyses from previous studies, confirms that epidote compositions vary significantly between magmatic-hydrothermal and metamorphic systems. Arsenic is higher in porphyry epidote, Bi is a distinctive tracer of skarn epidote and elevated Sn is characteristic of W-skarn systems. The LREE/HREE ratios in metamorphic epidote (< 5) are typically lower than in magmatic-hydrothermal epidote (> 5). Additionally, the Sn/HREE ratio discriminates epidote associated with W systems (> 25), Cu deposits (1–25) and metamorphic environments (< 1). Our findings confirm that epidote chemistry is a robust tool for evaluating ore potential and distinguishing skarn from porphyry and metamorphic systems.

A blind comparative study on isothermal sloshing in a circular tank (CCP-WSI Blind Test Series 5) - S.A. Brown; S.W. Colville; V. Francis; T. Zhao; Y.C. Lee; D. Cao; H. Chen; J. Chen; S. Chen; J. Davidson; J. Gong; H. Gu; et al. (Ocean Engineering, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Theta-aurora dynamics: Ionospheric mapping of evolving magnetospheric plasma boundaries - Xin-Ming Chen; Zan-Yang Xing; Qing-He Zhang; Yong-Liang Zhang; Hui-Gen Yang; L. R. Lyons; K. Oksavik; S. E. Milan; Rui-Long Guo; Tong Xu; Bin-Bin Tang; Xiang-Yu Wang; et al. (Science China Earth Sciences, 2026)
The theta-aurora, an auroral feature bridging the nightside and dayside auroral oval under a northward interplanetary magnetic field (IMF), is closely linked to the energetic plasma evolving within the magnetosphere. While existing views emphasize that energetic plasma resides on closed field lines, the mechanism by which it is accelerated and precipitates on open field lines to form the theta aurora remains poorly understood. Here, we introduce a mechanism derived from multi-instrument observations of theta-aurora evolution in the Northern Hemisphere and simulations conducted using a global magnetohydrodynamics (MHD) model. The observations and simulations exhibit excellent agreement, revealing that the theta-aurora represents ionospheric projections of boundaries between distinct magnetospheric plasma. These different magnetospheric plasma, an energetic structure originating from the plasma sheet and the preexisting cold lobe plasma, develop a boundary with contrasting physical properties that drive localized plasma instabilities. Particle precipitation occurs at plasma boundary, and controls both the formation and temporal evolution of theta-aurora. Our findings provide critical insights into the coupling between the ionosphere and magnetosphere under northward IMF.

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Exposure to diesel exhaust particles accelerated neuronal cell death in xenoferroptosis-susceptible cells - Hong Yan; Leshan Zhang; Daan P. Bergsma; Phoeja S. Gadjdjoe; Alessandra Tosato; Mohammad S. Rahman; Kristel Mulder; Joelle van Trigt; Karim Rafie; Christina H.T.J. Mol-van der Veen; Remco H.S. Westerink; Flemming R. Cassee; et al. (Journal of Environmental Sciences, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Analysis of Helium Monte Carlo Data for the ISS-CREAM Instrument - A. Bagga; S. Aggarwal; Y. Amare; D. Angelaszek; D.P. Bowman; Y.C. Chen; G.H. Choi; M. Copley; L. Derome; Z.M. Dorris; L. Eraud; J.H. Han; et al. (Advances in Space Research, 2026)

Delta-X: An airborne remote sensing framework to calibrate hydrodynamic and ecogeomorphic processes responsible for land building in coastal deltas - Marc Simard; Cathleen E. Jones; Robert R. Twilley; Edward Castañeda-Moya; Sergio Fagherazzi; Cédric G. Fichot; Michael P. Lamb; Paola Passalacqua; Tamlin M. Pavelsky; David R. Thompson; Saoussen Belhadj-aissa; Pradipta Biswas; et al. (Remote Sensing of Environment, 2026)

Daily evolution of VOCs in Beijing: chemistry, emissions, transport, and policy implications - Marios Panagi; Roberto Sommariva; Zoë L. Fleming; Paul S. Monks; Gongda Lu; Eloise A. Marais; James R. Hopkins; Alastair C. Lewis; Qiang Zhang; James D. Lee; Freya A. Squires; Lisa K. Whalley; et al. (Atmospheric Pollution Research, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Human versus machine: Can generative AI anticipate insect biological control outcomes? - Kris A.G. Wyckhuys; Komivi S. Akutse; Divina M. Amalin; Salah-Eddin Araj; Marie Joy B. Beltran; Ibtissem Ben Fekih; Paul-André Calatayud; Lizette Cicero; Marcellin C. Cokola; Yelitza C. Colmenarez; Kenza Dessauvages; Thomas Dubois; et al. (Computers and Electronics in Agriculture, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Dissection of Fusarium head blight resistance in a modified nested association mapping panel of synthetic and bread wheat germplasm - Anil Karmacharya; Dhondup Lhamo; Krishna Acharya; Qijun Zhang; Han-Chang Chang; Shaobin Zhong; Andrew J. Green; Jason D. Fiedler; Mingcheng Luo; Kirk M. Anderson; Amanda R. Peters Haugrud; Elias M. Elias; et al. (Theoretical and Applied Genetics, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Integrating legumes to enhance cereal production: The relative inputs of fertiliser nitrogen and legume biological nitrogen fixation in major wheat and maize producing countries - Mark B. Peoples; Xiaoxi Li; John A. Kirkegaard; Roger D. Armstrong; Ignacio A. Ciampitti; Angelinus C. Franke; Ken E. Giller; James R. Hunt; Marie-Hélène Jeuffroy; Jagdish K. Ladha; Gilles Lemaire; Long Li; et al. (Plant and Soil, 2026)
Background Cereal crops dominate arable agriculture and underpin global food supply. Cereal grain yield is closely related to crop nitrogen (N) uptake. However, excessive inputs of N fertiliser in cereal production systems can have negative environmental consequences and represent high financial risk for farmers. Scope This review explores opportunities to reduce the current reliance of the global staples, wheat ( Triticum aestivum ) and maize ( Zea mays ), on N fertiliser by diversifying cereal-based cropping systems with legumes, in both time (rotation) and space (via intercropping). Increases in cereal grain yield and N uptake resulting from the inclusion of legumes in wheat and maize cropping systems are examined across different geographic regions. The role of grain legumes and legume-based forages, cover-crops and green manures is described for the 15 countries responsible for producing > 70% of the world’s wheat and maize and consuming > 80% of the global applications of N fertiliser to these two cereals. Estimates of the contributions from biological N 2 fixation and legume residual N to cropping soils are provided for individual countries and compared to the N offtake in wheat and maize grain and the quantities of N fertiliser applied. The potential increased area of legumes required for the returns of legume N to match the current amounts of N removed in grain or supplied as fertiliser is assessed for each country, and the strategies that might be necessary to encourage farmers to increase the frequency of legumes used in cereal-dominated cropping systems are outlined.

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Cryopreservation of fish ovarian tissue post-mortem: Solution for emergency genetic preservation - Thaiza R. de Freitas; Lis S. Marques; Raquel S. dos Santos; Renata V. Dantas; Thales S. França; Rômulo B. Rodrigues; Karel G. Torres Lozano; Eduardo Albuquerque; Diógenes H. Siqueira-Silva; Tiantian Zhang; Danilo P. Streit (Cryobiology, 2025)

Evaluation of multimodel averaging approaches for ensembling evapotranspiration and yield simulations from maize models - Viveka Nand; Zhiming Qi; Liwang Ma; Matthew J. Helmers; Chandra A. Madramootoo; Ward N. Smith; Tiequan Zhang; Tobias K.D. Weber; Elizabeth Pattey; Ziwei Li; Jiaxin Wang; Virginia L. Jin; et al. (Journal of Hydrology, 2025)

Corrigendum to “Advanced aspects of acetogens” [Bioresour. Technol. 427 (2025) 131913] - Anja Poehlein; Benjamin Zeldes; Maximilian Flaiz; Tim Böer; Alina Lüschen; Franziska Höfele; Kira S. Baur; Bastian Molitor; Christian Kröly; Meng Wang; Quan Zhang; Yixuan Fan; et al. (Bioresource Technology, 2025)

Increased plasma concentrations of 6-oxo-methylphenidate in CES1 G134E carriers following a single oral dose of methylphenidate - Qingchen Zhang; Philip W. Melchert; Ahmed Awad; Christopher R. McCurdy; Beth Krone; Jeffrey Newcorn; Tanya E. Froehlich; Mark A. Stein; Josephine Raeuscher; Hao-Jie Zhu; John S. Markowitz (Medicinal Chemistry Research, 2025)

Provenance analysis of late Pleistocene sediment from IODP site U1477 reveals climate and river basin dynamics in the Zambezi river catchment - Youhong Gao; Hucai Zhang; Xiaonan Zhang; Lizeng Duan; Huayong Li; Ian R. Hall; Sidney R. Hemming; Leah J. LeVay; Junsheng Nie; Xibin Han; S. Barker; M.A. Berke; et al. (Gondwana Research, 2025)

A balanced approach to the potential of octopus aquaculture - Ian G. Gleadall; Roger Villanueva; Gregory J. Barord; Zoe Doubleday; Felipe Aguado-Giménez; Nobuhiko Akiyama; Eduardo Almansa; Cheryl L. Ames; Alexander Arkhipkin; Otilio Avendaño; Chris Barrett; Giambattista Bello; et al. (Marine Policy, 2025)

LP-40 Launch of the DIM testing project: when animal testing is difficult, impossible and meaningless (DIM) and implications for REACH regulation - M. van Velthoven; G. Pallocca; J. Ingram; V. Aranda; A. Bergqvist; M. Blanco-Rubio; K. Bonnot; B. Carrick; J. Dawick; N. Fabre; M. Fuart-Gatnik; R. Gozalbes; et al. (Toxicology Letters, 2025)

Introgression of stem rust resistance gene Sr68 from Thinopyrum junceum into wheat - Swarupa Nanda Mandal; Baljeet K. Gill; Zhixia Niu; Qijun Zhang; Daryl L. Klindworth; Santiago Bataller; Matthew N. Rouse; Yue Jin; Richard R. C. Wang; Xiwen Cai; Xiaofei Zhang; Roger Thilmony; et al. (Theoretical and Applied Genetics, 2025)

ATF4 in proximal tubules modulates kidney function and modifies the metabolome - Yuling Chi; Eduardo Mere Del Aguila; Tuo Zhang; Charles D. Warren; Helen R. Hoxie; Qiuying Chen; Steven S. Gross; Jacob B. Geri; David M. Nanus; Lorraine J. Gudas (Journal of Molecular Medicine, 2025)
Activating transcription factor 4 (ATF4) is a transcription factor that mediates the response to stress at the cellular, tissue, and organism level. We deleted the gene encoding ATF4 in the proximal tubules of the mouse kidney by using a temporal and cell type-specific approach. We show that ATF4 plays a major role in regulating the transcriptome and proteome, which, in turn, influences the metabolome and kidney functions. Genome-wide transcriptomics and single-plot, solid-phase-enhanced sample preparation (SP3)-proteomics studies reveal that ATF4 deletion changes more than 30% of transcripts and, similarly, corresponding proteins in the proximal tubules. Gene Set Enrichment Analysis indicates major changes in transporters, including amino acid transporters. Metabolomic analyses show that these changes in transporters are associated with altered profiles of amino acids in the blood, kidney, and urine. Stable isotope glutamine tracing in primary tubule cells isolated from kidney cortices confirms that ATF4 regulates glutamine transport and metabolism. We suggest that even in the absence of additional stresses, such as kidney injury, ATF4 in the proximal tubules modulates both retention of specific nutrients and excretion of catabolic products like creatinine to maintain normal kidney function. Key messages Activating transcription factor 4 (ATF4) deletion changed more than 30% of genome-wide transcripts and corresponding proteins in the proximal tubules. One set of the profound changes occurred in amino acid transporters and Slc22 family transporters. Changes in transporters were accompanied by altered profiles of amino acids and wastes in the blood, kidney, and urine. ATF4 in the kidney proximal tubules plays a key role in regulating both the reabsorption of nutrients and the excretion of wastes.

Impact of Terrestrial Weather on the Space Weather of the Ionosphere-Thermosphere: Initial Results from a NASA Living with a Star Focused Science Topic - J. Oberheide; D. Aggarwal; B. Bergsson; S. Chakraborty; S. Debchoudhury; M. Dhadly; F. Gasperini; L. Goncharenko; V. L. Harvey; C. Heale; P. Inchin; J. Li; et al. (Surveys in Geophysics, 2025)
The ionosphere-thermosphere (IT) is a convergence point of energy and processes that interconnect Earth’s atmosphere with space. Processes generated by terrestrial weather in the lower atmosphere (i.e., troposphere and stratosphere, altitudes less than ~ 50 km) are recognized by the scientific community as sources of variability in both the structure and composition of the IT. Exposed to persistent wave forcing from terrestrial weather sources and solar and magnetic forcing, the IT is a domain of compelling scientific inquiry that connects thermodynamics, fluid dynamics, electrodynamics and plasma physics. Predicting its space weather is of significant national interest for space situation awareness including the very low earth orbit as the new frontier of space operations. Advancing the understanding of whole atmosphere interconnections between terrestrial and space weather requires coordinated modeling and observational efforts across different spatial and temporal scales. Toward this goal, the National Aeronautics and Space Administration (NASA), through the living with a star (LWS) program, established in 2022 a focused science topic (FST) to study the problem from various angles. In this manuscript we report on the vision, goals and status of the ongoing FST “Impact of Terrestrial Weather on the Ionosphere—Thermosphere”. Initial results show bigger impacts on the IT than hitherto thought and help to more clearly define the state-of-the-art in the context of future NASA missions such as EZIE, DYNAMIC and GDC.

New insights into the middle Eocene environmental conditions and biogeographic setting of the Fergana Basin (Central Asia): Micropaleontological approaches - Yaroslav S. Trubin; Alina Winkler; Ilja Kogan; Andreas Brosig; Jingwen Zhang; Moriaki Yasuhara; Skye Yunshu Tian; Vladimir A. Marinov; Martin R. Langer (Journal of Asian Earth Sciences, 2025)

Advanced aspects of acetogens - Anja Poehlein; Benjamin Zeldes; Maximilian Flaiz; Tim Böer; Alina Lüschen; Franziska Höfele; Kira S. Baur; Bastian Molitor; Christian Kröly; Meng Wang; Quan Zhang; Yixuan Fan; et al. (Bioresource Technology, 2025)

Effects of atmospheric pollution and vegetation on nitrogen and phosphorus content in agri-forest watersheds under climate - S. Xi; H. Liu; J. Zhang; R. He; S. Jiang (International Journal of Environmental Science and Technology, 2025)

Degradation characteristics and reaction mechanism of supercritical water oxidation of oily wastewater - Y. Duan; S. Wang; L. Ding; R. Liu; Z. Li; H. Liu; F. Zhang; Y. Li; Y. Wang (International Journal of Environmental Science and Technology, 2025)

Analysis of the slope damage characteristics of the Xiluodu Hydropower Station during the impoundment period - K. Ma; D. Y. Guo; J. Wu; R. L. Wang; H. L. Huang; S. C. Zhang; G. He (Bulletin of Engineering Geology and the Environment, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Multi-instrument sounding of a Jovian thunderstorm from Juno - Shawn R. Brueshaber; Zhimeng Zhang; John H. Rogers; Gerald Eichstädt; Glenn S. Orton; Davide Grassi; Leigh N. Fletcher; Cheng Li; Shinji Mizumoto; Alessandro Mura; Fabiano Oyafuso; Ramanakumar Sankar; et al. (Icarus, 2025)

Fossil leaf cuticle: Best practices for preparation and paleo-CO2 analysis - Xiaoqing Zhang; Dana L. Royer; Carina E. Colombi; Juan Martin Drovandi; Jennifer C. McElwain; Gaëtan Guignard; Qin Leng; Barry H. Lomax; Nathan D. Sheldon; Rebekah A. Stein; Garland R. Upchurch; Yongdong Wang; et al. (Earth-Science Reviews, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Pets and related allergens modify the association between early life DEHP exposure and respiratory outcomes in children - Luyao Zhang; Ruixue Dai; Wendy Lou; Piush Mandhane; Theo J. Moraes; Elinor Simons; Peter S. Thorne; Teresa To; Stuart E. Turvey; Padmaja Subbarao; Jeffrey R. Brook (Environmental Research, 2025)

Uncertainty quantification for severe-accident reactor modelling: Results and conclusions of the MUSA reactor applications work package - S. Brumm; F. Gabrielli; V. Sanchez Espinoza; A. Stakhanova; P. Groudev; P. Petrova; P. Vryashkova; P. Ou; W. Zhang; A. Malkhasyan; L.E. Herranz; R. Iglesias Ferrer; et al. (Annals of Nuclear Energy, 2025)

Dissolved oxygen criteria attainment in Chesapeake Bay: Where has it improved since 1985? - Qian Zhang; Rebecca R. Murphy; Richard Tian; Kaylyn S. Gootman; Peter J. Tango (Science of The Total Environment, 2024)

A Transcriptomic Comparative Study of Cranial Vasculature - Jianing Zhang; Jee-Yeon Ryu; Selena-Rae Tirado; Lawrence D. Dickinson; Aviva Abosch; M. Ali Aziz-Sultan; Alan S. Boulos; Daniel L. Barrow; H. Hunt Batjer; Tamar R. Binyamin; Spiros L. Blackburn; Edward F. Chang; et al. (Translational Stroke Research, 2024)

Short duration heatwaves increase body temperature and alter blood gas balance but may not cause oxidative stress and intestinal structure variations in lambs - Minghao Zhang; Frank R. Dunshea; Robyn D. Warner; Kristy DiGiacomo; Aleena Joy; Archana Abhijith; Pragna Prathap; Ting Ma; Surinder S. Chauhan (Small Ruminant Research, 2024)

Expanded PAH analysis of household air pollution in a rural region of China with high lung cancer incidence - Yongliang Zhang; Kees Meliefste; Wei Hu; Lützen Portengen; Nathaniel Rothman; Boris Reiss; Jihua Li; Jun Xu; Baofu Ning; Dingyu Liu; Flemming R. Cassee; Jason Y.Y. Wong; et al. (Environmental Pollution, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A comprehensive molecular phylogeny of the terrestrial Parasitengona (Acariformes, Prostigmata) provides insights into the evolution of their metamorphosis, invasion into aquatic habitats and classification - Samuel G.S. Costa; Andrei Tolstikov; Alireza Saboori; Dante Batista-Ribeiro; Javad Noei; Mark S. Harvey; Matthew D. Shaw; Pavel B. Klimov; Zhi-Qiang Zhang; Almir R. Pepato (Molecular Phylogenetics and Evolution, 2024)

Evaluation of Slow-Releasing Energy Material (SREMA) Injection for In-Situ Rock Breaking Under Uniaxial and Triaxial Loading: An Experimental Study - U. I. Manatunga; P. G. Ranjith; V. R. S. De Silva; T. Xu; D. Zhang (Rock Mechanics and Rock Engineering, 2024)
Permeability enhancement of impervious rock formations is crucial for the exploitation of ore deposits, which are uneconomic using conventional mining methods. These deposits have the potential to be mined with in-situ recovery (ISR) mining methods, provided the deposit’s permeability is enhanced artificially. Slow-releasing energy material (SREMA) has been identified as a promising preconditioning technique to enhance rock permeability for ISR. However, the fracturing potential of SREMA in the presence of in-situ stresses remains under-explored in laboratory experimental research studies and needs to be assessed in detail prior to field trials. A unique confining cell was developed in this study to represent realistic confining stresses underground, and the impacts of different stress conditions on the fracturing potential of SREMA were investigated. In addition, the effects of SREMA expansion in pre-existing joints were also assessed using laboratory fracturing experiments conducted by injecting SREMA into sandstone specimens with artificially created horizontal persistent joints, which is the first attempt to the best of the author’s knowledge. Under uniaxial stress conditions (10 MPa), multiple radial cracks emerged from the borehole at the centre of the specimen, while vertical splitting of the specimen was observed due to the outward expansion of SREMA inside the joint. In comparison, under triaxial confinement (5 MPa and 10 MPa), a decrease in the damage caused to the rock mass due to the expansive pressure generated by SREMA was observed, and this was overcome by introducing multiple injection holes and stress relief holes into the rock mass.

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Greywater treatment using lab-scale systems combining trickling filters and constructed wetlands with recycled foam glass and water spinach - T.T. Nguyen; Z. Zhang; R. Wang; K. Sawada; S. Soda (Bioresource Technology Reports, 2024)

Corrigendum: Ocean surface radiation measurement best practices - Laura D. Riihimaki; Meghan F. Cronin; Raja Acharya; Nathan Anderson; John A. Augustine; Kelly A. Balmes; Patrick Berk; Roberto Bozzano; Anthony Bucholtz; Kenneth J. Connell; Christopher J. Cox; Alcide G. di Sarra; et al. (Frontiers in Marine Science, 2024)

Pyrrhotites in asteroid 162173 Ryugu: Records of the initial changes on their surfaces with aqueous alteration - Hiroharu Yui; Shu-hei Urashima; Morihiko Onose; Mayu Morita; Shintaro Komatani; Izumi Nakai; Yoshinari Abe; Yasuko Terada; Hisashi Homma; Kazuko Motomura; Kiyohiro Ichida; Tetsuya Yokoyama; et al. (Geochimica et Cosmochimica Acta, 2024)

The new kid on the block in insect pest management: sprayable RNAi goes commercial - Junjie Yan; Ralf Nauen; Stuart Reitz; Andrei Alyokhin; Jiang Zhang; David Mota-Sanchez; Yonggyun Kim; Subba Reddy Palli; Silvia I. Rondon; Brian A. Nault; Juan Luis Jurat-Fuentes; Michael S. Crossley; et al. (Science China Life Sciences, 2024)

Long‐term data reveal that grazer density mediates climatic stress in salt marshes - Carter S. Smith; Y. Stacy Zhang; Marc J. S. Hensel; Steven C. Pennings; Brian R. Silliman (Ecology, 2024)
Understanding how climate and local stressors interact is paramount for predicting future ecosystem structure. The effects of multiple stressors are often examined in small‐scale and short‐term field experiments, limiting understanding of the spatial and temporal generality of the findings. Using a 22‐year observational dataset of plant and grazer abundance in a southeastern US salt marsh, we analyzed how changes in drought and grazer density combined to affect plant biomass. We found: (1) increased drought severity and higher snail density both correlated with lower plant biomass; (2) drought and snail effects interacted additively; and, (3) snail effects had a threshold, with additive top‐down effects only occurring when snails were present at high densities. These results suggest that the emergence of multiple stressor effects can be density dependent, and they validate short‐term experimental evidence that consumers can augment environmental stress. These findings have important implications for predicting future ecosystem structure and managing natural ecosystems.

Reliable callus-induced plantlet regeneration from leaf explants of Lagerstroemia speciosa and genetic fidelity assessment through ISSR markers - Bin Wu; Nicholas S. Zhang; Benjamin Dixon; Ivan Sierra; Sofya Kan; Alanna Layton; Mengmeng Gu; Margaret R. Pooler; Hui Duan; Hongmin Qin (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Biocontrol of strawberry Botrytis gray mold and prolong the fruit shelf-life by fumigant Trichoderma spp. - Q. S. Fan; H. J. Lin; Y. J. Hu; J. Jin; H. H. Yan; R. Q. Zhang (Biotechnology Letters, 2024)

Ocean surface radiation measurement best practices - Laura D. Riihimaki; Meghan F. Cronin; Raja Acharya; Nathan Anderson; John A. Augustine; Kelly A. Balmes; Patrick Berk; Roberto Bozzano; Anthony Bucholtz; Kenneth J. Connell; Christopher J. Cox; Alcide G. di Sarra; et al. (Frontiers in Marine Science, 2024)
Ocean surface radiation measurement best practices have been developed as a first step to support the interoperability of radiation measurements across multiple ocean platforms and between land and ocean networks. This document describes the consensus by a working group of radiation measurement experts from land, ocean, and aircraft communities. The scope was limited to broadband shortwave (solar) and longwave (terrestrial infrared) surface irradiance measurements for quantification of the surface radiation budget. Best practices for spectral measurements for biological purposes like photosynthetically active radiation and ocean color are only mentioned briefly to motivate future interactions between the physical surface flux and biological radiation measurement communities. Topics discussed in these best practices include instrument selection, handling of sensors and installation, data quality monitoring, data processing, and calibration. It is recognized that platform and resource limitations may prohibit incorporating all best practices into all measurements and that spatial coverage is also an important motivator for expanding current networks. Thus, one of the key recommendations is to perform interoperability experiments that can help quantify the uncertainty of different practices and lay the groundwork for a multi-tiered global network with a mix of high-accuracy reference stations and lower-cost platforms and practices that can fill in spatial gaps.

Isolation and characterization of lytic bacteriophages infecting Pectobacterium atrosepticum - J. Wu; J. Liu; S. Liu; U. Handique; Q. Sun; Z. Feng; R. Zhang (European Journal of Plant Pathology, 2024)

Aspirin use and head and neck cancer survival and recurrence - Xinman Zhang; Omar S. Ilyas; Kayla R. Getz; Laura S. Rozek; Jeremy M. G. Taylor; Steven B. Chinn; Gregory T. Wolf; Alison M. Mondul (Cancer Causes & Control, 2024)

Uncovering the magnitude of African pangolin poaching with extensive nanopore DNA genotyping of seized scales - Darren Yeo; Amy H. J. Chan; Kum Chew Hiong; Jasmine Ong; Jun Yuan Ng; Jie Min Lim; Wendy Zhang; Sara R. Lim; Charlene J. Fernandez; Anna M‐S. Wong; Benjamin P. Y‐H. Lee; Max D. Y. Khoo; et al. (Conservation Biology, 2024)
Trade in pangolins is illegal, and yet tons of their scales and products are seized at various ports. These large seizures are challenging to process and comprehensively genotype for upstream provenance tracing and species identification for prosecution. We implemented a scalable DNA barcoding pipeline in which rapid DNA extraction and MinION sequencing were used to genotype a substantial proportion of pangolin scales subsampled from 2 record shipments seized in Singapore in 2019 (37.5 t). We used reference sequences to match the scales to phylogeographical regions of origin. In total, we identified 2346 cytochrome b ( cytb ) barcodes of white‐bellied ( Phataginus tricuspis ) (from 1091 scales), black‐bellied ( Phataginus tetradactyla ) (227 scales), and giant ( Smutsia gigantea ) (1028 scales) pangolins. Haplotype diversity was higher for P. tricuspis scales (121 haplotypes, 66 novel) than that for P. tetradactyla (22 haplotypes, 15 novel) and S. gigantea (25 haplotypes, 21 novel) scales. Of the novel haplotypes, 74.2% were likely from western and west‐central Africa, suggesting potential resurgence of poaching and newly exploited populations in these regions. Our results illustrate the utility of extensively subsampling large seizures and outline an efficient molecular approach for rapid genetic screening that should be accessible to most forensic laboratories and enforcement agencies.

Vegetation−fire feedbacks increase subtropical wildfire risk in scrubland and reduce it in forests - P. Wei; B. Lamont; T. He; W. Xue; P.C. Wang; W. Song; R. Zhang; A.B. Keyhani; S. Zhao; W. Lu; F. Dong; R. Gao; et al. (Journal of Environmental Management, 2024)

Pervasive aqueous alteration in the early Solar System revealed by potassium isotopic variations in Ryugu samples and carbonaceous chondrites - Yan Hu; Frédéric Moynier; Wei Dai; Marine Paquet; Tetsuya Yokoyama; Yoshinari Abe; Jérôme Aléon; Conel M. O'D. Alexander; Sachiko Amari; Yuri Amelin; Ken-ichi Bajo; Martin Bizzarro; et al. (Icarus, 2024)

Aboveground wheat biomass estimation from a low-altitude UAV platform based on multimodal remote sensing data fusion with the introduction of terrain factors - Shao-Hua Zhang; Li He; Jian-Zhao Duan; Shao-Long Zang; Tian-Cong Yang; U. R. S. Schulthess; Tian-Cai Guo; Chen-Yang Wang; Wei Feng (Precision Agriculture, 2024)

Characteristics and the possible origins of selenium in surface soil in Lanling County, Shandong Province, China - Q. H. Deng; Y. Zhao; S. Li; Y. S. Zhang; Q. R. Meng; F. Q. Li; H. P. Guo; Q. Chen; X. W. Y. Wang (International Journal of Environmental Science and Technology, 2024)

Dimension does matter: carbon-based substances with different dimensions exhibit opposite effects on soil CO2 and CH4 production - L. Zhou; X. Li; P. Zhang; J. Liu; M. Zhou; R. Dang; D.-V. N. Vo; P. S. Kumar (International Journal of Environmental Science and Technology, 2024)

Vertical migration and variation of crude oil in soil around typical oilfields under natural leaching - H. Chen; Y. Hao; S. L. Zhang; J. R. Pan; M. F. Lang; X. T. Guo (International Journal of Environmental Science and Technology, 2024)

Advanced treatment of domestic sewage through ceramic ultrafiltration, catalytic ozonation and activated carbon adsorption in pilot-scale study - J. L. Zhang; J. G. Zhang; J. X. Zhang; S. Sun; H. Su; X. Zheng; R. T. Liu (International Journal of Environmental Science and Technology, 2024)

Surface ocean warming near the core of hurricane Sam and its representation in forecast models - Andrew M. Chiodi; Hristina Hristova; Gregory R. Foltz; Jun A. Zhang; Calvin W. Mordy; Catherine R. Edwards; Chidong Zhang; Christian Meinig; Dongxiao Zhang; Edoardo Mazza; Edward D. Cokelet; Eugene F. Burger; et al. (Frontiers in Marine Science, 2024)
On September 30, 2021, a saildrone uncrewed surface vehicle intercepted Hurricane Sam in the northwestern tropical Atlantic and provided continuous observations near the eyewall. Measured surface ocean temperature unexpectedly increased during the first half of the storm. Saildrone current shear and upper-ocean structure from the nearest Argo profiles show an initial trapping of wind momentum by a strong halocline in the upper 30 m, followed by deeper mixing and entrainment of warmer subsurface water into the mixed layer. The ocean initial conditions provided to operational forecast models failed to capture the observed upper-ocean structure. The forecast models failed to simulate the warming and developed a surface cold bias of ~0.5°C by the time peak winds were observed, resulting in a 12-17% underestimation of surface enthalpy flux near the eyewall. Results imply that enhanced upper-ocean observations and, critically, improved assimilation into the hurricane forecast systems, could directly benefit hurricane intensity forecasts.

Evaluation of pollutant removal efficiency of urban stormwater wet ponds and the application of machine learning algorithms - Yang Yang; David Z. Zhu; Mark R. Loewen; Sherif S. Ahmed; Wenming Zhang; Haibin Yan; Bert van Duin; Khizar Mahmood (Science of The Total Environment, 2023)

Global online trade in primates for pets - Vincent Nijman; Thais Q. Morcatty; Hani R. El Bizri; Hassan Al-Razi; Andie Ang; Ahmad Ardiansyah; Sadek Atoussi; Daniel Bergin; Sarah Bell; Franciany Braga-Pereira; Marco Campera; Nabajit Das; et al. (Environmental Development, 2023)

Protocols for the seminal cryopreservation of South American catfishes – current status - Danilo P. Streit; Rômulo B. Rodrigues; Eduardo A. Sanches; Jayme A. Povh; Diógenes H. Siqueira-Silva; Thaíza R. de Freitas; Nathalia T. Santos; Jhony B. Lisboa; Thales S. França; Eduardo Nicoleti; Larise O.C. Lima; Tiantian Zhang (Cryobiology, 2023)

Anaerobic degradation of atrazine and desalkyl-atrazine by vitamin B12 under different pH: kinetics and degradation pathway - Y. Song; S. Sun; M. Wang; Q. Zhao; T. Zhang; R. Jia (International Journal of Environmental Science and Technology, 2023)

Validation of key sponge symbiont pathways using genome‐centric metatranscriptomics - Paul A. O'Brien; Shangjin Tan; Pedro R. Frade; Steven J. Robbins; J. Pamela Engelberts; Sara C. Bell; Inka Vanwonterghem; David J. Miller; Nicole S. Webster; Guojie Zhang; David G. Bourne (Environmental Microbiology, 2023)
The sponge microbiome underpins host function through provision and recycling of essential nutrients in a nutrient poor environment. Genomic data suggest that carbohydrate degradation, carbon fixation, nitrogen metabolism, sulphur metabolism and supplementation of B‐vitamins are central microbial functions. However, validation beyond the genomic potential of sponge symbiont pathways is rarely explored. To evaluate metagenomic predictions, we sequenced the metagenomes and metatranscriptomes of three common coral reef sponges: Ircinia ramosa , Ircinia microconulosa and Phyllospongia foliascens . Multiple carbohydrate active enzymes were expressed by Poribacteria, Bacteroidota and Cyanobacteria symbionts, suggesting these lineages have a central role in assimilating dissolved organic matter. Expression of entire pathways for carbon fixation and multiple sulphur compound transformations were observed in all sponges. Gene expression for anaerobic nitrogen metabolism (denitrification and nitrate reduction) were more common than aerobic metabolism (nitrification), where only the I. ramosa microbiome expressed the nitrification pathway. Finally, while expression of the biosynthetic pathways for B‐vitamins was common, the expression of additional transporter genes was far more limited. Overall, we highlight consistencies and disparities between metagenomic and metatranscriptomic results when inferring microbial activity, while uncovering new microbial taxa that contribute to the health of their sponge host via nutrient exchange.

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

An in vitro evaluation of kratom (Mitragyna speciosa) on the catalytic activity of carboxylesterase 1 (CES1) - Philip W. Melchert; Qingchen Zhang; Sushobhan Mukhopadhyay; Siva Rama Raju Kanumuri; Christopher R. McCurdy; John S. Markowitz (Chemico-Biological Interactions, 2023)

Florida-California Cancer Health Equity Center (CaRE2) Community Scientist Research Advocacy Program - B. Hensel; N. Askins; E. Ibarra; C. Aristizabal; I. Guzman; R. Barahona; B. Hazelton-Glenn; J. Lee; Z. Zhang; F. Odedina; D. J. Wilkie; M. C. Stern; et al. (Journal of Cancer Education, 2023)
The Community Scientist Program (CSP), a model connecting researchers with community members, is effective to inform and involve the general population in health-related clinical research. Given the existing cancer disparities among Black/African American and Hispanic/Latino/a populations, more models describing how cancer-related CSPs are designed, implemented, and evaluated are needed. The Florida-California Cancer Research, Education and Engagement (CaRE 2 ) Health Equity Center is a tri-institutional, bicoastal center created to eliminate cancer health disparities among Black/African American and Hispanic/Latino/a populations living in California and in Florida. The CaRE 2 Center created a Community Scientist Research Advocacy (CSRA) training program for community members to become cancer research advocates. The CSRA program is currently a 13-week program conducted 100% virtually with all materials provided in English and Spanish for participants to learn more about prostate, lung, and pancreas cancers, ongoing research at CaRE 2 , and ways to share cancer research throughout their communities. Participants attend didactic lectures on cancer research during weeks 1–5. In week 4, participants join CSRA self-selected groups based on cancer-related topics of interest. Each group presents their cancer-related advocacy project developed during weeks 5–12 at the final session. In this paper, we describe the CaRE 2 Health Equity Center’s CSRA program, share results, and discuss opportunities for improvement in future program evaluation as well as replication of this model in other communities.

P25-15: Construction, evaluation, and AOP framework-based application of EpPRS as a genetic surrogate for environmental pollutants - S. Chen; M. Du; J. Xin; R. Zheng; Z. Zhang; M. Wang (Toxicology Letters, 2023)

Survey of New Zealand consumer attitudes to consumption of meat and meat alternatives - C.E. Realini; T. Driver; R. Zhang; M. Guenther; S. Duff; C.R. Craigie; C. Saunders; M.M. Farouk (Meat Science, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

Multi-scale policy diffusion of marine emissions governance - Yiqi Zhang; Christine Loh; Gerald R. Patchell; Kellee S. Tsai (Marine Policy, 2023)

Error-corrected next generation sequencing – Promises and challenges for genotoxicity and cancer risk assessment - Francesco Marchetti; Renato Cardoso; Connie L. Chen; George R. Douglas; Joanne Elloway; Patricia A. Escobar; Tod Harper; Robert H. Heflich; Darren Kidd; Anthony M. Lynch; Meagan B. Myers; Barbara L. Parsons; et al. (Mutation Research - Reviews in Mutation Research, 2023)

Survival and predictive modeling of Listeria monocytogenes under simulated human gastric conditions in the presence of bovine milk products - Linkang Zhang; Valeria R. Parreira; Ashrafur Rahman; Ben A. Smith; Daniel S. Munther; Jeffrey M. Farber (International Journal of Food Microbiology, 2023)

Stratification and its consequences in two constructed urban stormwater wetlands - Sherif S. Ahmed; Wenming Zhang; Mark R. Loewen; David Z. Zhu; Tadros R. Ghobrial; Khizar Mahmood; Bert van Duin (Science of The Total Environment, 2023)

Galectin-3-centered paracrine network mediates cardiac inflammation and fibrosis upon β-adrenergic insult - Guomin Hu; Jimin Wu; Huijun Gu; Xiangning Deng; Wenli Xu; Shan Feng; Shuaixing Wang; Yao Song; Zhengda Pang; Xiuling Deng; Aleksandr E. Vendrov; Nageswara R. Madamanchi; et al. (Science China Life Sciences, 2023)

DsrC is involved in fermentative growth and interacts directly with the FlxABCD–HdrABC complex in Desulfovibrio vulgaris Hildenborough - Delfim Ferreira; Sofia S. Venceslau; Raquel Bernardino; André Preto; Lichun Zhang; Jacob R. Waldbauer; William D. Leavitt; Inês A. C. Pereira (Environmental Microbiology, 2023)
DsrC is a key protein in dissimilatory sulfur metabolism, where it works as co‐substrate of the dissimilatory sulfite reductase DsrAB. DsrC has two conserved cysteines in a C‐terminal arm that are converted to a trisulfide upon reduction of sulfite. In sulfate‐reducing bacteria, DsrC is essential and previous works suggested additional functions beyond sulfite reduction. Here, we studied whether DsrC also plays a role during fermentative growth of Desulfovibrio vulgaris Hildenborough, by studying two strains where the functionality of DsrC is impaired by a lower level of expression (IPFG07) and additionally by the absence of one conserved Cys (IPFG09). Growth studies coupled with metabolite and proteomic analyses reveal that fermentation leads to lower levels of DsrC, but impairment of its function results in reduced growth by fermentation and a shift towards more fermentative metabolism during sulfate respiration. In both respiratory and fermentative conditions, there is increased abundance of the FlxABCD–HdrABC complex and Adh alcohol dehydrogenase in IPFG09 versus the wild type, which is reflected in higher production of ethanol. Pull‐down experiments confirmed a direct interaction between DsrC and the FlxABCD–HdrABC complex, through the HdrB subunit. Dissimilatory sulfur metabolism, where sulfur compounds are used for energy generation, is a key process in the ecology of anoxic environments, and is more widespread among bacteria than previously believed. Two central proteins for this type of metabolism are DsrAB dissimilatory sulfite reductase and its co‐substrate DsrC. Using physiological, proteomic and biochemical studies of Desulfovibrio vulgaris Hildenborough and mutants affected in DsrC functionality, we show that DsrC is also relevant for fermentative growth of this model organism and that it interacts directly with the soluble FlxABCD‐HdrABC complex that links the NAD(H) pool with dissimilatory sulfite reduction.

Hydrothermal alteration and corresponding reservoir significance of the Permian Emeishan basaltic lavas, west Sichuan, China - Y. B. Sun; Y. F. Zhang; A. H. Xi; Y. Tang; B. J. Zhang; S. Q. Pei; R. R. Li; H. Yin; Q. Zeng; H. Z. Qu; R. J. Zhou (Australian Journal of Earth Sciences, 2023)

Updated guidelines for gene nomenclature in wheat - S. A. Boden; R. A. McIntosh; C. Uauy; S. G. Krattinger; J. Dubcovsky; W. J. Rogers; X. C. Xia; E. D. Badaeva; A. R. Bentley; G. Brown-Guedira; M. Caccamo; L. Cattivelli; et al. (Theoretical and Applied Genetics, 2023)
Key message Here, we provide an updated set of guidelines for naming genes in wheat that has been endorsed by the wheat research community. Abstract The last decade has seen a proliferation in genomic resources for wheat, including reference- and pan-genome assemblies with gene annotations, which provide new opportunities to detect, characterise, and describe genes that influence traits of interest. The expansion of genetic information has supported growth of the wheat research community and catalysed strong interest in the genes that control agronomically important traits, such as yield, pathogen resistance, grain quality, and abiotic stress tolerance. To accommodate these developments, we present an updated set of guidelines for gene nomenclature in wheat. These guidelines can be used to describe loci identified based on morphological or phenotypic features or to name genes based on sequence information, such as similarity to genes characterised in other species or the biochemical properties of the encoded protein. The updated guidelines provide a flexible system that is not overly prescriptive but provides structure and a common framework for naming genes in wheat, which may be extended to related cereal species. We propose these guidelines be used henceforth by the wheat research community to facilitate integration of data from independent studies and allow broader and more efficient use of text and data mining approaches, which will ultimately help further accelerate wheat research and breeding.

Editorial: The society for environmental geochemistry and health (SEGH): 50 years and beyond - M. J. Watts; A. Argyraki; M. Barbieri; A. Brown; M. Button; R. Finkelman; G. Gibson; O. Humphrey; X. Huo; A. S. Hursthouse; B. Kaninga; P. Marinho Reis; et al. (Environmental Geochemistry and Health, 2023)
When the SEGH international board released a short editorial paper back in 2019, we described an aim to increase the membership offering, whilst improving the diversity of input regionally, by scientific discipline and to ensure greater and more regular contact across the regions from 2020 onwards. Wider aspirations described in 2019 (Watts et al. 2019) are discussed within this short communication at the end of 2021 to evaluate progress made. In particular, how the SEGH community adapted to the unprecedented circumstances that have challenged each and every one of us throughout the COVID-19 pandemic since early 2020 and are likely to influence our activities for the foreseeable future.

Changes in soil microbial diversity and community composition across bahiagrass and rhizoma peanut pastures - Adesuwa S. Erhunmwunse; Luana Mayara Dantas Queiroz; Kaile Zhang; Cheryl L. Mackowiak; Ann R. S. Blount; José C. B. Dubeux; Hui-Ling Liao (Biology and Fertility of Soils, 2023)

Search for CP violation and measurement of branching fractions and decay asymmetry parameters for Λ c + → Λ h + and Λ c + → Σ 0 h + ( h = K , π ) - L.K. Li; W. Shan; K. Kinoshita; I. Adachi; H. Aihara; D.M. Asner; H. Atmacan; T. Aushev; V. Babu; S. Bahinipati; Sw. Banerjee; P. Behera; et al. (Science Bulletin, 2023)

The interplay between Cs and K in Pseudanabaena catenata; from microbial bloom control strategies to bioremediation options for radioactive waters - Kejing Zhang; Lynn Foster; Dawn Buchanan; Victoria S. Coker; Jon K. Pittman; Jonathan R. Lloyd (Journal of Hazardous Materials, 2023)

Revelation of the sciences of traditional foods - Zhen Jia; Boce Zhang; Arnav Sharma; Nathalie S. Kim; Sonia M. Purohit; Madison M. Green; Michelle R. Roche; Emma Holliday; Hongda Chen (Food Control, 2023)

The effect of relative humidity on eddy covariance latent heat flux measurements and its implication for partitioning into transpiration and evaporation - Weijie Zhang; Martin Jung; Mirco Migliavacca; Rafael Poyatos; Diego G. Miralles; Tarek S. El-Madany; Marta Galvagno; Arnaud Carrara; Nicola Arriga; Andreas Ibrom; Ivan Mammarella; Dario Papale; et al. (Agricultural and Forest Meteorology, 2023)

Integrating oculomics with genomics reveals imaging biomarkers for preventive and personalized prediction of arterial aneurysms - Yu Huang; Cong Li; Danli Shi; Huan Wang; Xianwen Shang; Wei Wang; Xueli Zhang; Xiayin Zhang; Yijun Hu; Shulin Tang; Shunming Liu; Songyuan Luo; et al. (EPMA Journal, 2023)
Objective Arterial aneurysms are life-threatening but usually asymptomatic before requiring hospitalization. Oculomics of retinal vascular features (RVFs) extracted from retinal fundus images can reflect systemic vascular properties and therefore were hypothesized to provide valuable information on detecting the risk of aneurysms. By integrating oculomics with genomics, this study aimed to (i) identify predictive RVFs as imaging biomarkers for aneurysms and (ii) evaluate the value of these RVFs in supporting early detection of aneurysms in the context of predictive, preventive and personalized medicine (PPPM). Methods This study involved 51,597 UK Biobank participants who had retinal images available to extract oculomics of RVFs. Phenome-wide association analyses (PheWASs) were conducted to identify RVFs associated with the genetic risks of the main types of aneurysms, including abdominal aortic aneurysm (AAA), thoracic aneurysm (TAA), intracranial aneurysm (ICA) and Marfan syndrome (MFS). An aneurysm-RVF model was then developed to predict future aneurysms. The performance of the model was assessed in both derivation and validation cohorts and was compared with other models employing clinical risk factors. An RVF risk score was derived from our aneurysm-RVF model to identify patients with an increased risk of aneurysms. Results PheWAS identified a total of 32 RVFs that were significantly associated with the genetic risks of aneurysms. Of these, the number of vessels in the optic disc (‘ntreeA’) was associated with both AAA ( β = −0.36, P = 6.75e−10) and ICA ( β = −0.11, P = 5.51e−06). In addition, the mean angles between each artery branch (‘curveangle_mean_a’) were commonly associated with 4 MFS genes ( FBN1 : β = −0.10, P = 1.63e−12; COL16A1 : β = −0.07, P = 3.14e−09; LOC105373592 : β = −0.06, P = 1.89e−05; C8orf81/LOC441376 : β = 0.07, P = 1.02e−05). The developed aneurysm-RVF model showed good discrimination ability in predicting the risks of aneurysms. In the derivation cohort, the C -index of the aneurysm-RVF model was 0.809 [95% CI: 0.780–0.838], which was similar to the clinical risk model (0.806 [0.778–0.834]) but higher than the baseline model (0.739 [0.733–0.746]). Similar performance was observed in the validation cohort, with a C -index of 0.798 (0.727–0.869) for the aneurysm-RVF model, 0.795 (0.718–0.871) for the clinical risk model and 0.719 (0.620–0.816) for the baseline model. An aneurysm risk score was derived from the aneurysm-RVF model for each study participant. The individuals in the upper tertile of the aneurysm risk score had a significantly higher risk of aneurysm compared to those in the lower tertile (hazard ratio = 17.8 [6.5–48.8], P = 1.02e−05). Conclusion We identified a significant association between certain RVFs and the risk of aneurysms and revealed the impressive capability of using RVFs to predict the future risk of aneurysms by a PPPM approach. Our finds have great potential to support not only the predictive diagnosis of aneurysms but also a preventive and more personalized screening plan which may benefit both patients and the healthcare system. Graphical abstract

Formation Processes of Gully-side Debris-Cones Determined from Ground-Penetrating Radar (Mt. Unzen, Japan) - C. Gomez; N. Hotta; Y. Shinohara; J.-H. Park; H. Tsunetaka; M. Zhang; B. Bradak; D. Sri Hadmoko; S. Budi Wibowo; R. Daikai; M. Yoshida (Journal of Applied Geophysics, 2023)

Holocene forcing of East Asian hydroclimate recorded in a subtropical peatland from southeastern China - Xianyu Huang; Hongbin Zhang; Michael L. Griffiths; Bingyan Zhao; Francesco S. R. Pausata; Clay Tabor; Junwu Shu; Shucheng Xie (Climate Dynamics, 2023)

A regime shift in the Southeast Greenland marine ecosystem - Mads Peter Heide‐Jørgensen; Philippine Chambault; Teunis Jansen; Caroline V. B. Gjelstrup; Aqqalu Rosing‐Asvid; Andreas Macrander; Gísli Víkingsson; Xiangdong Zhang; Camilla S. Andresen; Brian R. MacKenzie (Global Change Biology, 2023)
Two major oceanographic changes have recently propagated through several trophic levels in coastal areas of Southeast Greenland (SEG). Firstly, the amount of drift‐ice exported from the Fram Strait and transported with the East Greenland Current (EGC) has decreased significantly over the past two decades, and a main tipping element (summer sea ice) has virtually disappeared since 2003 leading to a regime shift in oceanographic and ecological conditions in the region. The following 20‐year period with low or no coastal sea ice is unique in the 200‐year history of ice observations in the region, and the regime shift is also obvious in the volume of ice export through the Fram Strait after 2013. In the same period, the temperature of the EGC south of 73.5 N has increased significantly (>2°C) since 1980. Secondly, the warm Irminger Current, which advects warm, saline Atlantic Water into the region, has become warmer since 1990. The lack of pack ice in summer together with a warming ocean generated cascading effects on the ecosystem in SEG that are manifested in a changed fish fauna with an influx of boreal species in the south and the subarctic capelin further north. At higher trophic levels there has been an increase in the abundance of several boreal cetaceans (humpback, fin, killer, and pilot whales and dolphins) that are either new to this area or occur in historically large numbers. It is estimated that the new cetacean species in SEG are responsible for an annual predation level of 700,000 tons of fish. In addition, predation on krill species is estimated at >1,500,000 tons mainly consumed by fin whales. Simultaneously, there has been a reduction in the abundance and catches of narwhals and walruses in SEG and it is suggested that these species have been impacted by the habitat changes.

Emotional responses of piglets under long-term exposure to negative and positive auditory stimuli - H.-Y. Nian; R.-X. Zhang; S.-S. Ding; Y.-L. Wang; J.-F. Li; H.-G. Liu; J.-H. Li; X. Li; J. Bao (Domestic Animal Endocrinology, 2023)

Correction to: Extracellular Vesicles Derived from Neural Progenitor Cells––a Preclinical Evaluation for Stroke Treatment in Mice - X. Zheng; L. Zhang; Y. Kuang; V. Venkataramani; F. Jin; K. Hein; M. P. Zafeiriou; C. Lenz; W. Moebius; E. Kilic; D. M. Hermann; M. S. Weber; et al. (Translational Stroke Research, 2022)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

A 10-miRNA risk score-based prediction model for pathological complete response to neoadjuvant chemotherapy in hormone receptor-positive breast cancer - Chang Gong; Ziliang Cheng; Yaping Yang; Jun Shen; Yingying Zhu; Li Ling; Wanyi Lin; Zhigang Yu; Zhihua Li; Weige Tan; Chushan Zheng; Wenbo Zheng; et al. (Science China Life Sciences, 2022)

Uterine fibroid polygenic risk score (PRS) associates and predicts risk for uterine fibroid - Jacqueline A. Piekos; Jacklyn N. Hellwege; Yanfei Zhang; Eric S. Torstenson; Gail P. Jarvik; Ozan Dikilitas; Iftikhar J. Kullo; Daniel J. Schaid; David R. Crosslin; Sarah A. Pendergrass; Ming Ta Michael Lee; Dan Roden; et al. (Human Genetics, 2022)

A 130‐year global inventory of methane emissions from livestock: Trends, patterns, and drivers - Lei Zhang; Hanqin Tian; Hao Shi; Shufen Pan; Jinfeng Chang; Shree R. S. Dangal; Xiaoyu Qin; Siyuan Wang; Francesco N. Tubiello; Josep G. Canadell; Robert B. Jackson (Global Change Biology, 2022)
Livestock contributes approximately one‐third of global anthropogenic methane (CH 4 ) emissions. Quantifying the spatial and temporal variations of these emissions is crucial for climate change mitigation. Although country‐level information is reported regularly through national inventories and global databases, spatially explicit quantification of century‐long dynamics of CH 4 emissions from livestock has been poorly investigated. Using the Tier 2 method adopted from the 2019 Refinement to 2006 IPCC guidelines, we estimated CH 4 emissions from global livestock at a spatial resolution of 0.083° (~9 km at the equator) during the period 1890–2019. We find that global CH 4 emissions from livestock increased from 31.8 [26.5–37.1] (mean [minimum−maximum of 95% confidence interval) Tg CH 4 yr −1 in 1890 to 131.7 [109.6–153.7] Tg CH 4 yr −1 in 2019, a fourfold increase in the past 130 years. The growth in global CH 4 emissions mostly occurred after 1950 and was mainly attributed to the cattle sector. Our estimate shows faster growth in livestock CH 4 emissions as compared to the previous Tier 1 estimates and is ~20% higher than the estimate from FAOSTAT for the year 2019. Regionally, South Asia, Brazil, North Africa, China, the United States, Western Europe, and Equatorial Africa shared the majority of the global emissions in the 2010s. South Asia, tropical Africa, and Brazil have dominated the growth in global CH 4 emissions from livestock in the recent three decades. Changes in livestock CH 4 emissions were primarily associated with changes in population and national income and were also affected by the policy, diet shifts, livestock productivity improvement, and international trade. The new geospatial information on the magnitude and trends of livestock CH 4 emissions identifies emission hotspots and spatial–temporal patterns, which will help to guide meaningful CH 4 mitigation practices in the livestock sector at both local and global scales.

Proceedings of the fifth international Molecular Pathological Epidemiology (MPE) meeting - Song Yao; Peter T. Campbell; Tomotaka Ugai; Gretchen Gierach; Mustapha Abubakar; Viktor Adalsteinsson; Jonas Almeida; Paul Brennan; Stephen Chanock; Todd Golub; Samir Hanash; Curtis Harris; et al. (Cancer Causes & Control, 2022)

GeoSoilEnviroCARS (Sector 13) at the Advanced Photon Source: a comprehensive synchrotron radiation facility for Earth science research at ambient and extreme conditions - S. R. Sutton; M. L. Rivers; S. Chariton; P. J. Eng; A. Lanzirotti; M. Newville; T. Officer; V. B. Prakapenka; Y. J. Ryu; J. E. Stubbs; S. Tkachev; Y. Wang; et al. (Physics and Chemistry of Minerals, 2022)

Geographical contrasts of Y‐chromosomal haplogroups from wild and domestic goats reveal ancient migrations and recent introgressions - Isaäc J. Nijman; Benjamin D. Rosen; Philippe Bardou; Thomas Faraut; Tristan Cumer; Kevin G. Daly; Zhuqing Zheng; Yudong Cai; Hojjat Asadollahpour; Bengi Çınar Kul; Wei‐Yi Zhang; Guangxin E.; et al. (Molecular Ecology, 2022)
By their paternal transmission, Y‐chromosomal haplotypes are sensitive markers of population history and male‐mediated introgression. Previous studies identified biallelic single‐nucleotide variants in the SRY , ZFY and DDX3Y genes, which in domestic goats identified four major Y‐chromosomal haplotypes, Y1A, Y1B, Y2A and Y2B, with a marked geographical partitioning. Here, we extracted goat Y‐chromosomal variants from whole‐genome sequences of 386 domestic goats (75 breeds) and seven wild goat species, which were generated by the VarGoats goat genome project. Phylogenetic analyses indicated domestic haplogroups corresponding to Y1B, Y2A and Y2B, respectively, whereas Y1A is split into Y1AA and Y1AB. All five haplogroups were detected in 26 ancient DNA samples from southeast Europe or Asia. Haplotypes from present‐day bezoars are not shared with domestic goats and are attached to deep nodes of the trees and networks. Haplogroup distributions for 186 domestic breeds indicate ancient paternal population bottlenecks and expansions during migrations into northern Europe, eastern and southern Asia, and Africa south of the Sahara. In addition, sharing of haplogroups indicates male‐mediated introgressions, most notably an early gene flow from Asian goats into Madagascar and the crossbreeding that in the 19th century resulted in the popular Boer and Anglo‐Nubian breeds. More recent introgressions are those from European goats into the native Korean goat population and from Boer goat into Uganda, Kenya, Tanzania, Malawi and Zimbabwe. This study illustrates the power of the Y‐chromosomal variants for reconstructing the history of domestic species with a wide geographical range.

Exceptional heat and atmospheric dryness amplified losses of primary production during the 2020 U.S. Southwest hot drought - Matthew P. Dannenberg; Dong Yan; Mallory L. Barnes; William K. Smith; Miriam R. Johnston; Russell L. Scott; Joel A. Biederman; John F. Knowles; Xian Wang; Tomer Duman; Marcy E. Litvak; John S. Kimball; et al. (Global Change Biology, 2022)
Earth's ecosystems are increasingly threatened by “hot drought,” which occurs when hot air temperatures coincide with precipitation deficits, intensifying the hydrological, physiological, and ecological effects of drought by enhancing evaporative losses of soil moisture (SM) and increasing plant stress due to higher vapor pressure deficit (VPD). Drought‐induced reductions in gross primary production (GPP) exert a major influence on the terrestrial carbon sink, but the extent to which hotter and atmospherically drier conditions will amplify the effects of precipitation deficits on Earth's carbon cycle remains largely unknown. During summer and autumn 2020, the U.S. Southwest experienced one of the most intense hot droughts on record, with record‐low precipitation and record‐high air temperature and VPD across the region. Here, we use this natural experiment to evaluate the effects of hot drought on GPP and further decompose those negative GPP anomalies into their constituent meteorological and hydrological drivers. We found a 122 Tg C (>25%) reduction in GPP below the 2015–2019 mean, by far the lowest regional GPP over the Soil Moisture Active Passive satellite record. Roughly half of the estimated GPP loss was attributable to low SM (likely a combination of record‐low precipitation and warming‐enhanced evaporative depletion), but record‐breaking VPD amplified the reduction of GPP, contributing roughly 40% of the GPP anomaly. Both air temperature and VPD are very likely to continue increasing over the next century, likely leading to more frequent and intense hot droughts and substantially enhancing drought‐induced GPP reductions.

Understanding the Sources of Heavy Metal Pollution in Ambient Air of Neighboring a Solid Waste Landfill Site - Umangi H. Mehta; Daya S. Kaul; Dane Westerdahl; Zhi Ning; Kai Zhang; Li Sun; Peng Wei; Hardik H. Gajjar; Jai D. Jeyaraman; Mansi V. Patel; Rutu R. Joshi (Aerosol Science and Engineering, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Boron isotopes of white mica and tourmaline in an ultra-high pressure metapelite from the western Tianshan, China: dehydration and metasomatism during exhumation of subducted ocean-floor sediments - J. Xu; G. B. Zhang; H. R. Marschall; J. B. Walters; S. Q. Liu; Z. Lü; L. F. Zhang; H. Hu; N. Li (Contributions to Mineralogy and Petrology, 2022)

Seasonal Variation of Methane Fluxes in a Mangrove Ecosystem in South India: An Eddy Covariance-Based Approach - Palingamoorthy Gnanamoorthy; S. Chakraborty; R. Nagarajan; R. Ramasubramanian; V. Selvam; Pramit Kumar Deb Burman; P. Partha Sarathy; Mohd Zeeshan; Qinghai Song; Yiping Zhang (Estuaries and Coasts, 2022)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Overall and central obesity and prostate cancer risk in African men - Ilir Agalliu; Wei-Kaung Jerry Lin; Janice S. Zhang; Judith S. Jacobson; Thomas E. Rohan; Ben Adusei; Nana Yaa F. Snyper; Caroline Andrews; Elkhansa Sidahmed; James E. Mensah; Richard Biritwum; Andrew A. Adjei; et al. (Cancer Causes & Control, 2022)

Invertebrate Grazing on Live Turtlegrass (Thalassia testudinum): A Common Interaction That May Facilitate Fungal Growth - Anjali D. Boyd; Nia S. Walker; Stephanie R. Valdez; Y. Stacy Zhang; Andrew H. Altieri; Vladislav Gulis; Caitlin Crain; Brian Silliman (Frontiers in Marine Science, 2022)
In coastal wetlands and tropical reefs, snails can regulate foundation species by feeding on marsh grasses and hard corals. In many cases, their impacts are amplified because they facilitate microbial infection in grazer-induced wounds. Whether snails commonly graze live plants and facilitate microbial growth on plants in tropical seagrass systems is less explored. On a Belizean Caye, we examined patterns in snail-generated grazer scars on the abundant turtlegrass ( Thalassia testudinum ). Our initial survey showed the occurrence of snail-induced scarring on live turtlegrass blades was common, with 57% of live leaves scarred. Feeding trials demonstrated that two of five common snails ( Tegula fasciata– smooth tegula and Smaragdia viridis –emerald nerite) grazed unepiphytized turtlegrass blades and that smooth tegula abundance had a positive relationship with scarring intensity. Subsequent surveys at three Caribbean sites (separated by >150 km) also showed a high occurrence of snail-induced scars on turtlegrass blades. Finally, simulated herbivory experiments and field observations of a turtlegrass bed in Florida, United States suggests that herbivore damage could facilitate fungal growth in live seagrass tissue through mechanical opening of tissue. Combined, these findings reveal that snail grazing on live turtlegrass blades in the Caribbean can be common. Based on these results, we hypothesize that small grazers could be exerting top-down control over turtlegrass growth directly via grazing and/or indirectly by facilitating microbial infection in live seagrass tissue. Further studies are needed to determine the generality and relative importance of direct and indirect effects of gastropod grazing on turtlegrass health.

Antidepressant activity of pharmacological and genetic deactivation of the small-conductance calcium-activated potassium channel subtype-3 - Mina G. Nashed; Shannon Waye; S. M. Nageeb Hasan; Diana Nguyen; Micaela Wiseman; Jing Zhang; Harry Lau; O. Chandani Dinesh; Roger Raymond; Iain R. Greig; Francis Rodriguez Bambico; José N. Nobrega (Psychopharmacology, 2022)

Integrated pest management of Tuta absoluta: practical implementations across different world regions - Nicolas Desneux; Peng Han; Ramzi Mansour; Judit Arnó; Thierry Brévault; Mateus R. Campos; Anais Chailleux; Raul N. C. Guedes; Javad Karimi; Kouassi Arthur J. Konan; Anne-violette Lavoir; María G. Luna; et al. (Journal of Pest Science, 2022)

Towards a global list of accepted species III. Independence and stakeholder inclusion - Stijn Conix; Stephen T. Garnett; Kevin R. Thiele; Les Christidis; Peter Paul van Dijk; Olaf S. Bánki; Saroj K. Barik; John S. Buckeridge; Mark J. Costello; Donald Hobern; Paul M. Kirk; Aaron Lien; et al. (Organisms Diversity & Evolution, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Incursions of divergent genotypes, evolution of virulence and host jumps shape a continental clonal population of the stripe rust pathogen Puccinia striiformis - Yi Ding; Will S. Cuddy; Colin R. Wellings; Peng Zhang; Tine Thach; Mogens S. Hovmøller; Dinah Qutob; Gurcharn S. Brar; Hadley R. Kutcher; Robert F. Park (Molecular Ecology, 2021)
Long‐distance migration and host adaptation by transboundary plant pathogens often brings detrimental effects to important agroecosystems. Efficient surveillance as a basis for responding to the dynamics of such pathogens is often hampered by a lack of information on incursion origin, evolutionary pathways and the genetic basis of rapidly evolving virulence across larger timescales. Here, we studied these genetic features by using historical isolates of the obligate biotrophic pathogen Puccinia striiformis f. sp. tritici ( Pst ), which causes one of the most widespread and devastating diseases, stripe (yellow) rust, of wheat. Through a combination of genotypic, phenotypic and genomic analyses, we assigned eight Pst isolates representing putative exotic Pst incursions into Australia to four previously defined genetic groups, PstS0, PstS1, PstS10 and PstS13. We showed that isolates of an additional incursion of P . striiformis , known locally as P . striiformis f. sp. pseudo ‐ hordei , had a new and unique multilocus SSR genotype (MLG). We provide results of overall genomic variation of representative Pst isolates from each genetic group by comparative genomic analyses. We showed that isolates within the PstS1 and PstS13 genetic groups are most distinct at the whole‐genome variant level from isolates belonging to genetic group PstS0, whereas the isolate from the PstS10 genetic group is intermediate. We further explored variable gene content, including putative effectors, representing both shared but also unique genetic changes that have occurred following introduction, some of which may additionally account for local adaptation of these isolates to triticale. Our genotypic and genomic data revealed new genetic insights into the evolution of diverse phenotypes of rust pathogens following incursion into a geographically isolated continental region.

Overexpression of Panax ginseng defensin enhances resistance to Fusarium solani in transgenic Arabidopsis thaliana - T. Sun; Y. Zhang; Q. Wang; Y. Jiang; H. Li; R. Ma; S. Wang; Y. Zhao (Australasian Plant Pathology, 2021)

The Mechanical Response and Tolerance of the Anteriorly-Tilted Human Pelvis Under Vertical Loading - R. S. Salzar; E. M. Spratley; K. A. Henderson; P. C. Greenhalgh; J. Z. Zhang; B. J. Perry; J. A. McMahon (Annals of Biomedical Engineering, 2021)

University of Alabama at Birmingham Nathan Shock Center: comparative energetics of aging - Steven N. Austad; Thomas W. Buford; David B. Allison; Scott. W. Ballinger; Andrew W. Brown; Christy S. Carter; Victor M. Darley-Usmar; John L. Hartman; Timothy R. Nagy; Daniel L. Smith; Liou Sun; Jianhua Zhang (GeroScience, 2021)

Theory, methods, and operational results of the Young Women’s Health History Study: a study of young-onset breast cancer incidence in Black and White women - Ellen M. Velie; Lydia R. Marcus; Dorothy R. Pathak; Ann S. Hamilton; Ralph DiGaetano; Ron Klinger; Bibi Gollapudi; Richard Houang; Nicole Carnegie; L. Karl Olson; Amani Allen; Zhenzhen Zhang; et al. (Cancer Causes & Control, 2021)
Purpose The etiology of young-onset breast cancer (BC) is poorly understood, despite its greater likelihood of being hormone receptor-negative with a worse prognosis and persistent racial and socioeconomic inequities. We conducted a population-based case–control study of BC among young Black and White women and here discuss the theory that informed our study, exposures collected, study methods, and operational results. Methods Cases were non-Hispanic Black (NHB) and White (NHW) women age 20–49 years with invasive BC in metropolitan Detroit and Los Angeles County SEER registries 2010–2015. Controls were identified through area-based sampling from the U.S. census and frequency matched to cases on study site, race, and age. An eco-social theory of health informed life-course exposures collected from in-person interviews, including socioeconomic, reproductive, and energy balance factors. Measured anthropometry, blood (or saliva), and among cases SEER tumor characteristics and tumor tissue (from a subset of cases) were also collected. Results Of 5,309 identified potentially eligible cases, 2,720 sampled participants were screened and 1,812 completed interviews (682 NHB, 1140 NHW; response rate (RR): 60%). Of 24,612 sampled control households 18,612 were rostered, 2,716 participants were sampled and screened, and 1,381 completed interviews (665 NHB, 716 NHW; RR: 53%). Ninety-nine% of participants completed the main interview, 82% provided blood or saliva (75% blood only), and SEER tumor characteristics (including ER, PR and HER2 status) were obtained from 96% of cases. Conclusions Results from the successfully established YWHHS should expand our understanding of young-onset BC etiology overall and by tumor type and identify sources of racial and socioeconomic inequities in BC.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Geology and geochronology of the Two-Thirty prospect, Northparkes district, NSW - T. J. Wells; David R. Cooke; M. J. Baker; L. Zhang; S. Meffre; J. Steadman; M. D. Norman; J. L. Hoye (Australian Journal of Earth Sciences, 2021)

Discordant DNA mismatch repair protein status between synchronous or metachronous gastrointestinal carcinomas: frequency, patterns, and molecular etiologies - Monika Vyas; Canan Firat; Jaclyn F. Hechtman; Martin R. Weiser; Rona Yaeger; Chad Vanderbilt; Jamal K. Benhamida; Ajaratu Keshinro; Liying Zhang; Peter Ntiamoah; Marco Gonzalez; Rebecca Andrade; et al. (Familial Cancer, 2021)

Internal and external coupling of Gaussian mixture model and deep recurrent network for probabilistic drought forecasting - S. Zhu; Z. Xu; X. Luo; X. Liu; R. Wang; M. Zhang; Z. Huo (International Journal of Environmental Science and Technology, 2021)

Regional Differences in Antifungal Susceptibility of the Prevalent Dermatophyte Trichophyton rubrum - Y. Jiang; W. Luo; P. E. Verweij; Y. Song; B. Zhang; Z. Shang; A. M. S. Al-Hatmi; S. A. Ahmed; Z. Wan; R. Li; G. S. de Hoog (Mycopathologia, 2021)
In vitro susceptibility testing for Trichophyton rubrum has shown resistance to terbinafine, azoles and amorolfine, locally, but epidemiological cutoffs are not available. In order to assess the appropriateness of current first-line antifungal treatment for T. rubrum in China, we characterized antifungal susceptibility patterns of Chinese T. rubrum strains to nine antifungals and also described the upper limits of wild-type (WT) minimal inhibitory concentrations (MIC) (UL-WT) based on our study and another six studies published during the last decades. Sixty-two clinical isolates originating from seven provinces in China were identified as T. rubrum sensu stricto; all Chinese strains showed low MICs to eight out of nine antifungal drugs. Terbinafine (TBF) showed the lowest MICs of all antifungal classes tested in both the Chinese and global groups, with a 97.5% UL-WT MIC-value of 0.03 mg/L. No non-WT isolates were observed for TBF in China, but were reported in 18.5% of the global group. Our study indicated that TBF was still the most active drug for Chinese T. rubrum isolates, and all strains were within the WT-population. TBF therefore remains recommended for primary therapy to dermatophytosis caused by T. rubrum in China now, but regular surveillance of dermatophytes and antifungal susceptibility is recommended.

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Extracellular Vesicles Derived from Neural Progenitor Cells––a Preclinical Evaluation for Stroke Treatment in Mice - X. Zheng; L. Zhang; Y. Kuang; V. Venkataramani; F. Jin; K. Hein; M. P. Zafeiriou; C. Lenz; W. Moebius; E. Kilic; D. M. Hermann; M. S. Weber; et al. (Translational Stroke Research, 2021)
Stem cells such as mesenchymal stem cells (MSCs) enhance neurological recovery in preclinical stroke models by secreting extracellular vesicles (EVs). Since previous reports have focused on the application of MSC-EVs only, the role of the most suitable host cell for EV enrichment and preclinical stroke treatment remains elusive. The present study aimed to evaluate the therapeutic potential of EVs derived from neural progenitor cells (NPCs) following experimental stroke. Using the PEG technique, EVs were enriched and characterized by electron microscopy, proteomics, rt-PCR, nanosight tracking analysis, and Western blotting. Different dosages of NPC-EVs displaying a characteristic profile in size, shape, cargo protein, and non-coding RNA contents were incubated in the presence of cerebral organoids exposed to oxygen-glucose deprivation (OGD), significantly reducing cell injury when compared with control organoids. Systemic administration of NPC-EVs in male C57BL6 mice following experimental ischemia enhanced neurological recovery and neuroregeneration for as long as 3 months. Interestingly, the therapeutic impact of such NPC-EVs was found to be not inferior to MSC-EVs. Flow cytometric analyses of blood and brain samples 7 days post-stroke demonstrated increased blood concentrations of B and T lymphocytes after NPC-EV delivery, without affecting cerebral cell counts. Likewise, a biodistribution analysis after systemic delivery of NPC-EVs revealed the majority of NPC-EVs to be found in extracranial organs such as the liver and the lung. This proof-of-concept study supports the idea of EVs being a general concept of stem cell–induced neuroprotection under stroke conditions, where EVs contribute to reverting the peripheral post-stroke immunosuppression.

Techniques for In Vivo Measurement of Ligament and Tendon Strain: A Review - Qiang Zhang; Naomi C. Adam; S. H. Hosseini Nasab; William R. Taylor; Colin R. Smith (Annals of Biomedical Engineering, 2021)
The critical clinical and scientific insights achieved through knowledge of in vivo musculoskeletal soft tissue strains has motivated the development of relevant measurement techniques. This review provides a comprehensive summary of the key findings, limitations, and clinical impacts of these techniques to quantify musculoskeletal soft tissue strains during dynamic movements. Current technologies generally leverage three techniques to quantify in vivo strain patterns, including implantable strain sensors, virtual fibre elongation, and ultrasound. (1) Implantable strain sensors enable direct measurements of tissue strains with high accuracy and minimal artefact, but are highly invasive and current designs are not clinically viable. (2) The virtual fibre elongation method tracks the relative displacement of tissue attachments to measure strains in both deep and superficial tissues. However, the associated imaging techniques often require exposure to radiation, limit the activities that can be performed, and only quantify bone-to-bone tissue strains. (3) Ultrasound methods enable safe and non-invasive imaging of soft tissue deformation. However, ultrasound can only image superficial tissues, and measurements are confounded by out-of-plane tissue motion. Finally, all in vivo strain measurement methods are limited in their ability to establish the slack length of musculoskeletal soft tissue structures. Despite the many challenges and limitations of these measurement techniques, knowledge of in vivo soft tissue strain has led to improved clinical treatments for many musculoskeletal pathologies including anterior cruciate ligament reconstruction, Achilles tendon repair, and total knee replacement. This review provides a comprehensive understanding of these measurement techniques and identifies the key features of in vivo strain measurement that can facilitate innovative personalized sports medicine treatment.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

COSORE: A community database for continuous soil respiration and other soil‐atmosphere greenhouse gas flux data - Ben Bond‐Lamberty; Danielle S. Christianson; Avni Malhotra; Stephanie C. Pennington; Debjani Sihi; Amir AghaKouchak; Hassan Anjileli; M. Altaf Arain; Juan J. Armesto; Samaneh Ashraf; Mioko Ataka; Dennis Baldocchi; et al. (Global Change Biology, 2020)
Globally, soils store two to three times as much carbon as currently resides in the atmosphere, and it is critical to understand how soil greenhouse gas (GHG) emissions and uptake will respond to ongoing climate change. In particular, the soil‐to‐atmosphere CO 2 flux, commonly though imprecisely termed soil respiration ( R S ), is one of the largest carbon fluxes in the Earth system. An increasing number of high‐frequency R S measurements (typically, from an automated system with hourly sampling) have been made over the last two decades; an increasing number of methane measurements are being made with such systems as well. Such high frequency data are an invaluable resource for understanding GHG fluxes, but lack a central database or repository. Here we describe the lightweight, open‐source COSORE (COntinuous SOil REspiration) database and software, that focuses on automated, continuous and long‐term GHG flux datasets, and is intended to serve as a community resource for earth sciences, climate change syntheses and model evaluation. Contributed datasets are mapped to a single, consistent standard, with metadata on contributors, geographic location, measurement conditions and ancillary data. The design emphasizes the importance of reproducibility, scientific transparency and open access to data. While being oriented towards continuously measured R S , the database design accommodates other soil‐atmosphere measurements (e.g. ecosystem respiration, chamber‐measured net ecosystem exchange, methane fluxes) as well as experimental treatments (heterotrophic only, etc.). We give brief examples of the types of analyses possible using this new community resource and describe its accompanying R software package.

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Roles of dietary taurine in fish nutrition - W. W. H. A. Sampath; R. M. D. S. Rathnayake; Mengxi Yang; Wenbing Zhang; Kangsen Mai (Marine Life Science & Technology, 2020)

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

High-resolution Integrated Geophysical Investigation at the Lancaster Gold Mine, Krugersdorp, South Africa - E. O. Onyebueke; R. J. Durrheim; M. S. D. Manzi; S. Sebothoma; S. E. Zhang; E. Stettler (Pure and Applied Geophysics, 2020)

Impacts of heat stress on meat quality and strategies for amelioration: a review - Minghao Zhang; Frank R. Dunshea; Robyn D. Warner; Kristy DiGiacomo; R. Osei-Amponsah; Surinder S. Chauhan (International Journal of Biometeorology, 2020)

Downregulation of Salmonella Virulence Gene Expression During Invasion of Epithelial Cells Treated with Lactococcus lactis subsp. cremoris JFR1 Requires OppA - J. S. Zhang; M. Corredig; R. Morales-Rayas; A. Hassan; M. W. Griffiths; Gisèle LaPointe (Probiotics and Antimicrobial Proteins, 2020)

A comparison between water uptake and root length density in winter wheat: effects of root density and rhizosphere properties - X. X. Zhang; P. A. Whalley; R. W. Ashton; J. Evans; M. J. Hawkesford; S. Griffiths; Z. D. Huang; H. Zhou; S. J. Mooney; W. R. Whalley (Plant and Soil, 2020)
Background and aims We aim to quantify the variation in root distribution in a set of 35 experimental wheat lines. We also compared the effect of variation in hydraulic properties of the rhizosphere on water uptake by roots. Methods We measured the root length density and soil drying in 35 wheat lines in a field experiment. A 3D numerical model was used to predict soil drying profiles with the different root length distributions and compared with measured soil drying. The model was used to test different scenarios of the hydraulic properties of the rhizosphere. Results We showed that wheat lines with no detectable differences in root length density can induce soil drying profiles with statistically significant differences. Our data confirmed that a root length density of at least 1 cm/cm 3 is needed to drain all the available water in soil. In surface layers where the root length density was far greater than 1 cm/cm 3 water uptake was independent of rooting density due to competition for water. However, in deeper layers where root length density was less than 1 cm/cm 3 , water uptake by roots was proportional to root density. Conclusion In a set of wheat lines with no detectable differences in the root length density we found significant differences in water uptake. This may be because small differences in root density at depth can result in larger differences in water uptake or that the hydraulic properties of the rhizosphere can greatly affect water uptake.

Provenance analysis of the Cretaceous Laiyang Group on Lingshan Island (western Yellow Sea, China) and its tectono-sedimentary implications - A. P. Fan; S. N. Sun; R. C. Yang; Z. Zhang; S. De; J. D. N. Nenzhelele; Y. Li; H. P. Liu; Y. Q. Zhou; J. Yuan (Australian Journal of Earth Sciences, 2020)

Seabirds as environmental indicators: foraging behaviour and ecophysiology of common diving petrels (Pelecanoides urinatrix) reflect local-scale differences in prey availability - B. J. Dunphy; S. I. Vickers; J. Zhang; R. L. Sagar; T. J. Landers; S. J. Bury; A. J. R. Hickey; M. J. Rayner (Marine Biology, 2020)

Trends in vector-borne transmission efficiency from coinfected hosts: Grapevine leafroll-associated virus-3 and Grapevine virus A - G. K. Blaisdell; S. Zhang; A. Rowhani; V. Klaassen; M. L. Cooper; K. M. Daane; R. P. P. Almeida (European Journal of Plant Pathology, 2020)

Microbial dynamics and soil physicochemical properties explain large‐scale variations in soil organic carbon - Haicheng Zhang; Daniel S. Goll; Ying‐Ping Wang; Philippe Ciais; William R. Wieder; Rose Abramoff; Yuanyuan Huang; Bertrand Guenet; Anne‐Katrin Prescher; Raphael A. Viscarra Rossel; Pierre Barré; Claire Chenu; et al. (Global Change Biology, 2020)
First‐order organic matter decomposition models are used within most Earth System Models (ESMs) to project future global carbon cycling; these models have been criticized for not accurately representing mechanisms of soil organic carbon (SOC) stabilization and SOC response to climate change. New soil biogeochemical models have been developed, but their evaluation is limited to observations from laboratory incubations or few field experiments. Given the global scope of ESMs, a comprehensive evaluation of such models is essential using in situ observations of a wide range of SOC stocks over large spatial scales before their introduction to ESMs. In this study, we collected a set of in situ observations of SOC, litterfall and soil properties from 206 sites covering different forest and soil types in Europe and China. These data were used to calibrate the model MIMICS (The MIcrobial‐MIneral Carbon Stabilization model), which we compared to the widely used first‐order model CENTURY. We show that, compared to CENTURY, MIMICS more accurately estimates forest SOC concentrations and the sensitivities of SOC to variation in soil temperature, clay content and litter input. The ratios of microbial biomass to total SOC predicted by MIMICS agree well with independent observations from globally distributed forest sites. By testing different hypotheses regarding (using alternative process representations) the physicochemical constraints on SOC deprotection and microbial turnover in MIMICS, the errors of simulated SOC concentrations across sites were further decreased. We show that MIMICS can resolve the dominant mechanisms of SOC decomposition and stabilization and that it can be a reliable tool for predictions of terrestrial SOC dynamics under future climate change. It also allows us to evaluate at large scale the rapidly evolving understanding of SOC formation and stabilization based on laboratory and limited filed observation.

Automated volcanic hot-spot detection based on FY-4A/AGRI infrared data - S. S. Chu; L. Zhu; H. F. Sun; Q. W. Li; X. R. Zhang; T. T. Chen; L. Qiao; W. R. Zhu; D. X. Zhao; Y. H. Zhang (International Journal of Remote Sensing, 2020)

The Society for Environmental Geochemistry and Health (SEGH): building for the future - Michael J. Watts; Taicheng An; Ariadne Argyraki; Emmanuel Arhin; Anthea Brown; Mark Button; Jane A. Entwistle; Robert Finkelman; Gillian Gibson; Olivier S. Humphrey; Xia Huo; Andrew S. Hursthouse; et al. (Environmental Geochemistry and Health, 2020)

Antidepressant Drugs Correct the Imbalance Between proBDNF/p75NTR/Sortilin and Mature BDNF/TrkB in the Brain of Mice with Chronic Stress - C. R. Yang; X. Y. Zhang; Y. Liu; J. Y. Du; R. Liang; M. Yu; F. Q. Zhang; X. F. Mu; F. Li; L. Zhou; F. H. Zhou; F. J. Meng; et al. (Neurotoxicity Research, 2020)

Opioid-Induced Hyperalgesia Is Associated with Dysregulation of Circadian Rhythm and Adaptive Immune Pathways in the Mouse Trigeminal Ganglia and Nucleus Accumbens - Pan Zhang; Laura S. Moye; Bruce R. Southey; Isaac Dripps; Jonathan V. Sweedler; Amynah Pradhan; Sandra L. Rodriguez-Zas (Molecular Neurobiology, 2019)

Uncertainties in Long-Term Twenty-First Century Process-Based Coastal Sea-Level Projections - R. S. W. van de Wal; X. Zhang; S. Minobe; S. Jevrejeva; R. E. M. Riva; C. Little; K. Richter; M. D. Palmer (Surveys in Geophysics, 2019)
Many processes affect sea level near the coast. In this paper, we discuss the major uncertainties in coastal sea-level projections from a process-based perspective, at different spatial and temporal scales, and provide an outlook on how these uncertainties may be reduced. Uncertainty in centennial global sea-level rise is dominated by the ice sheet contributions. Geographical variations in projected sea-level change arise mainly from dynamical patterns in the ocean response and other geophysical processes. Finally, the uncertainties in the short-duration extreme sea-level events are controlled by near coastal processes, storms and tides.

Relative stability of the S2 isomers of the oxygen evolving complex of photosystem II - Divya Kaur; Witold Szejgis; Junjun Mao; Muhamed Amin; Krystle M. Reiss; Mikhail Askerka; Xiuhong Cai; Umesh Khaniya; Yingying Zhang; Gary W. Brudvig; Victor S. Batista; M. R. Gunner (Photosynthesis Research, 2019)

Blood transfusion history and risk of non-Hodgkin lymphoma: an InterLymph pooled analysis - James R. Cerhan; Eleanor Kane; Claire M. Vajdic; Martha S. Linet; Alain Monnereau; Leslie Bernstein; Silvia de Sanjose; Brian C.-H Chiu; John J. Spinelli; L. Dal Maso; Yawei Zhang; Beth R. Larrabee; et al. (Cancer Causes & Control, 2019)

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Taxonomy of the order Bunyavirales: update 2019 - Abulikemu Abudurexiti; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; et al. (Archives of Virology, 2019)

Genetic analysis of threshability and other spike traits in the evolution of cultivated emmer to fully domesticated durum wheat - Jyoti S. Sharma; Katherine L. D. Running; Steven S. Xu; Qijun Zhang; Amanda R. Peters Haugrud; Sapna Sharma; Phillip E. McClean; Justin D. Faris (Molecular Genetics and Genomics, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

The water cycle of the mid‐Holocene West African monsoon: The role of vegetation and dust emission changes - Gabriele Messori; Marco Gaetani; Qiang Zhang; Qiong Zhang; Francesco S. R. Pausata (International Journal of Climatology, 2019)
During the mid‐Holocene (6 kyr BP), West Africa experienced a much stronger and geographically extensive monsoon than in the present day. Changes in orbital forcing, vegetation and dust emissions from the Sahara have been identified as key factors driving this intensification. Here, we analyse how the timing, origin and convergence of moisture fluxes contributing to the monsoonal precipitation change under a range of scenarios: orbital forcing only; orbital and vegetation forcings (Green Sahara); orbital, vegetation and dust forcings (Green Sahara‐reduced dust). We further compare our results to a range of reconstructions of mid‐Holocene precipitation from palaeoclimate archives. In our simulations, the greening of the Sahara leads to a cyclonic water vapour flux anomaly over North Africa with an anomalous westerly flow bringing large amounts of moisture into the Sahel from the Atlantic Ocean. Changes in atmospheric dust under a vegetated Sahara shift the anomalous moisture advection pattern northwards, increasing both moisture convergence and precipitation recycling over the northern Sahel and Sahara and the associated precipitation during the boreal summer. During this season, under both the Green Sahara and Green Sahara‐reduced dust scenarios, local recycling in the Saharan domain exceeds that of the Sahel. This points to local recycling as an important factor modulating vegetation‐precipitation feedbacks and the impact of Saharan dust emissions. Our results also show that temperature and evapotranspiration over the Sahara in the mid‐Holocene are close to Sahelian pre‐industrial values. This suggests that pollen‐based paleoclimate reconstructions of precipitation during the Green Sahara period are likely not biased by possible large evapotranspiration changes in the region.

Complete sequencing of the SMN2 gene in SMA patients detects SMN gene deletion junctions and variants in SMN2 that modify the SMA phenotype - Corey Ruhno; Vicki L. McGovern; Matthew R. Avenarius; Pamela J. Snyder; Thomas W. Prior; Flavia C. Nery; Abdurrahman Muhtaseb; Jennifer S. Roggenbuck; John T. Kissel; Valeria A. Sansone; Jennifer J. Siranosian; Alec J. Johnstone; et al. (Human Genetics, 2019)

Taxonomy of the order Bunyavirales: second update 2018 - Piet Maes; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; Felicity J. Burt; et al. (Archives of Virology, 2019)

The Be-Well Study: a prospective cohort study of lifestyle and genetic factors to reduce the risk of recurrence and progression of non-muscle-invasive bladder cancer - Marilyn L. Kwan; Lawrence H. Kushi; Kim N. Danforth; Janise M. Roh; Isaac J. Ergas; Valerie S. Lee; Kimberly L. Cannavale; Teresa N. Harrison; Richard Contreras; Ronald K. Loo; David S. Aaronson; Charles P. Quesenberry; et al. (Cancer Causes & Control, 2019)

Unravelling the complexity of magma plumbing at Mount St. Helens: a new trace element partitioning scheme for amphibole - Madeleine C. S. Humphreys; George F. Cooper; Jing Zhang; Matthew Loewen; Adam J. R. Kent; Colin G. Macpherson; Jon P. Davidson (Contributions to Mineralogy and Petrology, 2019)

Climate change impact and adaptation for wheat protein - Senthold Asseng; Pierre Martre; Andrea Maiorano; Reimund P. Rötter; Garry J. O’Leary; Glenn J. Fitzgerald; Christine Girousse; Rosella Motzo; Francesco Giunta; M. Ali Babar; Matthew P. Reynolds; Ahmed M. S. Kheir; et al. (Global Change Biology, 2019)
Wheat grain protein concentration is an important determinant of wheat quality for human nutrition that is often overlooked in efforts to improve crop production. We tested and applied a 32‐multi‐model ensemble to simulate global wheat yield and quality in a changing climate. Potential benefits of elevated atmospheric CO 2 concentration by 2050 on global wheat grain and protein yield are likely to be negated by impacts from rising temperature and changes in rainfall, but with considerable disparities between regions. Grain and protein yields are expected to be lower and more variable in most low‐rainfall regions, with nitrogen availability limiting growth stimulus from elevated CO 2 . Introducing genotypes adapted to warmer temperatures (and also considering changes in CO 2 and rainfall) could boost global wheat yield by 7% and protein yield by 2%, but grain protein concentration would be reduced by −1.1 percentage points, representing a relative change of −8.6%. Climate change adaptations that benefit grain yield are not always positive for grain quality, putting additional pressure on global wheat production.

Differential cobalt-induced effects on plant growth, ultrastructural modifications, and antioxidative response among four Brassica napus (L.) cultivars - S. Ali; R. A. Gill; T. M. Mwamba; N. Zhang; M. T. Lv; Z. ul Hassan; F. Islam; S. Ali; W. J. Zhou (International Journal of Environmental Science and Technology, 2018)

Detecting hydrological consistency between soil moisture and precipitation and changes of soil moisture in summer over the Tibetan Plateau - X. Meng; R. Li; L. Luan; S. Lyu; T. Zhang; Y. Ao; B. Han; L. Zhao; Y. Ma (Climate Dynamics, 2018)

Reliability analysis of slope stability under seismic condition during a given exposure time - H. W. Huang; S. C. Wen; J. Zhang; F. Y. Chen; J. R. Martin; H. Wang (Landslides, 2018)

An Experimental Study of Fatigue Behavior of Granite Under Low-Cycle Repetitive Compressive Impacts - T. Zhou; S. L. Dong; G. F. Zhao; R. Zhang; S. Y. Wu; J. B. Zhu (Rock Mechanics and Rock Engineering, 2018)

Root and mycorrhizal fungal foraging responses to fruit removal in apple trees - Emily K. Lavely; Jianghong Zhang; Thomas S. Adams; David R. Bryla; Jared L. DeForest; Richard P. Marini; Robert Crassweller; David M. Eissenstat (Plant and Soil, 2018)

Predicting potato tuber yield loss due to early blight severity in the Midwestern United States - S. K. R. Yellareddygari; Raymond J. Taylor; Julie S. Pasche; Anqing Zhang; Neil C. Gudmestad (European Journal of Plant Pathology, 2018)

Modification of PPTA-based polymeric waste and adsorption properties for metal ions - J. J. Gao; R. J. Qu; S. S. Li; F. W. Pan; X. H. Jia; C. M. Sun; Y. Zhang; Q. L. Ma; C. X. Li (International Journal of Environmental Science and Technology, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Correction to: Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

Apoptosis and expression of apoptosis-related genes in mouse intestinal tissue after whole-body proton exposure - Ashley Purgason; Ye Zhang; Stanley R. Hamilton; Daila S. Gridley; Ayodotun Sodipe; Olufisayo Jejelowo; Govindarajan T. Ramesh; Maria Moreno-Villanueva; Honglu Wu (Molecular and Cellular Biochemistry, 2018)

Immunohistochemical null-phenotype for mismatch repair proteins in colonic carcinoma associated with concurrent MLH1 hypermethylation and MSH2 somatic mutations - Tao Wang; Zsofia K. Stadler; Liying Zhang; Martin R. Weiser; Olca Basturk; Jaclyn F. Hechtman; Efsevia Vakiani; Lenard B. Saltz; David S. Klimstra; Jinru Shia (Familial Cancer, 2018)

Does the major aluminium-resistance gene in wheat, TaALMT1, also confer tolerance to alkaline soils? - Carolina M. S. Silva; Chunyan Zhang; Gustavo Habermann; Emmanuel Delhaize; Peter R. Ryan (Plant and Soil, 2018)

(Im)mobilization of soil heavy metals using CaO, FA, sulfur, and Na2S: a 1-year incubation study - A. Mahar; P. Wang; A. Ali; A. H. Lahori; M. K. Awasthi; Z. Wang; Z. Guo; Q. Wang; S. Feng; R. Li; Z. Zhang (International Journal of Environmental Science and Technology, 2018)

Pyramidal cell-selective GluN1 knockout causes impairments in salience attribution and related EEG activity - Alexandra D. Forrest; Jakyung Bang; Robert E. Featherstone; Jonathan H. Bloom; Matthew S. Luminais; Rebecca V. Zhang; Christopher R. Gajewski; Mary F. McMullen; Yuling Liang; Steven J. Siegel (Experimental Brain Research, 2018)

Assessing associations between indoor environment and health symptoms in Romanian school children: an analysis of data from the SINPHONIE project - Jillian R. Palumbo; Shao Lin; Ziqiang Lin; Iulia A. Neamtiu; Wangjian Zhang; Eva Csobod; Eugen S. Gurzau (Environmental Science and Pollution Research, 2018)

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

LEFTY2 inhibits endometrial receptivity by downregulating Orai1 expression and store-operated Ca2+ entry - Madhuri S. Salker; Yogesh Singh; Ruban R. Peter Durairaj; Jing Yan; Md Alauddin; Ni Zeng; Jennifer H. Steel; Shaqiu Zhang; Jaya Nautiyal; Zoe Webster; Sara Y. Brucker; Diethelm Wallwiener; et al. (Journal of Molecular Medicine, 2018)

Methane emission from global livestock sector during 1890–2014: Magnitude, trends and spatiotemporal patterns - Shree R. S. Dangal; Hanqin Tian; Bowen Zhang; Shufen Pan; Chaoqun Lu; Jia Yang (Global Change Biology, 2017)
Human demand for livestock products has increased rapidly during the past few decades largely due to dietary transition and population growth, with significant impact on climate and the environment. The contribution of ruminant livestock to greenhouse gas ( GHG ) emissions has been investigated extensively at various scales from regional to global, but the long‐term trend, regional variation and drivers of methane ( CH 4 ) emission remain unclear. In this study, we use Intergovernmental Panel on Climate Change ( IPCC ) Tier II guidelines to quantify the evolution of CH 4 emissions from ruminant livestock during 1890–2014. We estimate that total CH 4 emissions in 2014 was 97.1 million tonnes (MT) CH 4 or 2.72 Gigatonnes (Gt) CO 2 ‐eq (1 MT = 10 12 g, 1 Gt = 10 15 g) from ruminant livestock, which accounted for 47%–54% of all non‐ CO 2 GHG emissions from the agricultural sector. Our estimate shows that CH 4 emissions from the ruminant livestock had increased by 332% (73.6 MT CH 4 or 2.06 Gt CO 2 ‐eq) since the 1890s. Our results further indicate that livestock sector in drylands had 36% higher emission intensity ( CH 4 emissions/km 2 ) compared to that in nondrylands in 2014, due to the combined effect of higher rate of increase in livestock population and low feed quality. We also find that the contribution of developing regions (Africa, Asia and Latin America) to the total CH 4 emissions had increased from 51.7% in the 1890s to 72.5% in the 2010s. These changes were driven by increases in livestock numbers ( LU units) by up to 121% in developing regions, but decreases in livestock numbers and emission intensity (emission/km 2 ) by up to 47% and 32%, respectively, in developed regions. Our results indicate that future increases in livestock production would likely contribute to higher CH 4 emissions, unless effective strategies to mitigate GHG emissions in livestock system are implemented.

Efficient Sugarcane Transformation via bar Gene Selection - W. Z. Wang; B. P. Yang; C. L. Feng; J. G. Wang; G. R. Xiong; T. T. Zhao; S. Z. Zhang (Tropical Plant Biology, 2017)

The application of lettuce in the qualitative and quantitative detection of Rhizoctonia Solani AG- 1 IA toxins - S. F. Ren; Z. Y. Zhang; W. H. Dong; W. J. Bao; R. Yue; L. Liu; C. Y. Li; G. H. Yang (Phytoparasitica, 2017)

Erratum to: Haploinsufficiency of the E3 ubiquitin-protein ligase gene TRIP12 causes intellectual disability with or without autism spectrum disorders, speech delay, and dysmorphic features - Jing Zhang; Tomasz Gambin; Bo Yuan; Przemyslaw Szafranski; Jill A. Rosenfeld; Mohammed Al Balwi; Abdulrahman Alswaid; Lihadh Al-Gazali; Aisha M. Al Shamsi; Makanko Komara; Bassam R. Ali; Elizabeth Roeder; et al. (Human Genetics, 2017)

Comparison of the Atlantic meridional overturning circulation between 1960 and 2007 in six ocean reanalysis products - A. R. Karspeck; D. Stammer; A. Köhl; G. Danabasoglu; M. Balmaseda; D. M. Smith; Y. Fujii; S. Zhang; B. Giese; H. Tsujino; A. Rosati (Climate Dynamics, 2017)

Effects of cell motility and morphology on the rheology of algae suspensions - N. Cagney; T. Zhang; R. Bransgrove; M. J. Allen; S. Balabani (Journal of Applied Phycology, 2017)

Effect of Feeding and Withdrawal of Vanadium and Vitamin C on Egg Quality and Vanadium Residual Over Time in Laying Hens - J. P. Wang; K. R. He; X. M. Ding; S. P. Bai; Q. F. Zeng; K. Y. Zhang (Biological Trace Element Research, 2017)

Haploinsufficiency of the E3 ubiquitin-protein ligase gene TRIP12 causes intellectual disability with or without autism spectrum disorders, speech delay, and dysmorphic features - Jing Zhang; Tomasz Gambin; Bo Yuan; Przemyslaw Szafranski; Jill A. Rosenfeld; Mohammed Al Balwi; Abdulrahman Alswaid; Lihadh Al-Gazali; Aisha M. Al Shamsi; Makanko Komara; Bassam R. Ali; Elizabeth Roeder; et al. (Human Genetics, 2017)

Quercetin induces protective autophagy and apoptosis through ER stress via the p-STAT3/Bcl-2 axis in ovarian cancer - Y. Liu; W. Gong; Z. Y. Yang; X. S. Zhou; C. Gong; T. R. Zhang; X. Wei; D. Ma; F. Ye; Q. L. Gao (Apoptosis, 2017)

Changes in flowering functional group affect responses of community phenological sequences to temperature change - F. D. Meng; L. L. Jiang; Z. H. Zhang; S. J. Cui; J. C. Duan; S. P. Wang; C. Y. Luo; Q. Wang; Y. Zhou; X. E. Li; L. R. Zhang; B. W. Li; et al. (Ecology, 2017)
Our ability to predict how temperature modifies phenology at the community scale is limited by our lack of understanding of responses by functional groups of flowering plants. These responses differ among species with different life histories. We performed a reciprocal transplant experiment along four elevation gradients (e.g., 3,200, 3,400, 3,600 and 3,800 m) to investigate the effects of warming (transferred downward) and cooling (transferred upward) on plant flowering functional groups (FFGs) and community phenological sequences (i.e., seven phenological events). Warming significantly decreased early‐spring‐flowering (ESF) plant coverage and increased mid‐summer‐flowering plant (MSF) coverage, while cooling had the opposite effect. All community phenological events were advanced by warming and delayed by cooling except for the date of complete leaf‐coloring, which showed the opposite response. Warming and cooling could cause greater advance or delay in early‐season phenological events of the community through increased coverage of MSF species, and warming could delay late‐season phenological events of the community by increased coverage of ESF species. These results suggested that coverage change of FFGs in the community induced by temperature change could mediate the responses of the community phenological events to temperature change in the future. The response of phenological events to temperature change at the species level may not be sufficient to predict phenological responses at the community‐level due to phenological compensation between species in the community.

Identification and functional characterisation of genetic variants in OLFM2 in children with developmental eye disorders - R. Holt; S. A. Ugur Iseri; A. W. Wyatt; D. A. Bax; D. Gold Diaz; C. Santos; S. Broadgate; R. Dunn; J. Bruty; Y. Wallis; D. McMullan; C. Ogilvie; et al. (Human Genetics, 2017)

Efficacy of N-Acetylserotonin and Melatonin in the EAE Model of Multiple Sclerosis - Jie Wen; Prasanth S. Ariyannur; Rachel Ribeiro; Mikiei Tanaka; John R. Moffett; Batool F. Kirmani; Aryan M.A. Namboodiri; Yumin Zhang (Journal of Neuroimmune Pharmacology, 2016)

Biomechanical Behavior of Bioprosthetic Heart Valve Heterograft Tissues: Characterization, Simulation, and Performance - Joao S. Soares; Kristen R. Feaver; Will Zhang; David Kamensky; Ankush Aggarwal; Michael S. Sacks (Cardiovascular Engineering and Technology, 2016)

What caused the spring intensification and winter demise of the 2011 drought over Texas? - D. Nelun Fernando; Kingtse C. Mo; Rong Fu; Bing Pu; Adam Bowerman; Bridget R. Scanlon; Ruben S. Solis; Lei Yin; Robert E. Mace; John R. Mioduszewski; Tong Ren; Kai Zhang (Climate Dynamics, 2016)

Moderate-intensity exercise alters markers of alternative activation in circulating monocytes in females: a putative role for PPARγ - J. S. Ruffino; N. A. Davies; K. Morris; M. Ludgate; L. Zhang; R. Webb; A. W. Thomas (European Journal of Applied Physiology, 2016)

Heterologous expression of the Hsp24 from Trichoderma asperellum improves antifungal ability of Populus transformant Pdpap-Hsp24 s to Cytospora chrysosperma and Alternaria alternate - S. D. Ji; Z. Y. Wang; H. J. Fan; R. S. Zhang; Z. Y. Yu; J. J. Wang; Z. H. Liu (Journal of Plant Research, 2016)

Multi-scale Modeling of the Cardiovascular System: Disease Development, Progression, and Clinical Intervention - Yanhang Zhang; Victor H. Barocas; Scott A. Berceli; Colleen E. Clancy; David M. Eckmann; Marc Garbey; Ghassan S. Kassab; Donna R. Lochner; Andrew D. McCulloch; Roger Tran-Son-Tay; Natalia A. Trayanova (Annals of Biomedical Engineering, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Assessing current genetic status of the Hainan gibbon using historical and demographic baselines: implications for conservation management of species of extreme rarity - J. V. Bryant; D. Gottelli; X. Zeng; X. Hong; B. P. L. Chan; J. R. Fellowes; Y. Zhang; J. Luo; C. Durrant; T. Geissmann; H. J. Chatterjee; S. T. Turvey (Molecular Ecology, 2016)
Evidence‐based conservation planning is crucial for informing management decisions for species of extreme rarity, but collection of robust data on genetic status or other parameters can be extremely challenging for such species. The Hainan gibbon, possibly the world's rarest mammal, consists of a single population of ~25 individuals restricted to one protected area on Hainan Island, China, and has persisted for over 30 years at exceptionally low population size. Analysis of genotypes at 11 microsatellite loci from faecal samples for 36% of the current global population and tissue samples from 62% of existing historical museum specimens demonstrates limited current genetic diversity ( Na = 2.27, Ar = 2.24, H e = 0.43); diversity has declined since the 19th century and even further within the last 30 years, representing declines of ~30% from historical levels ( Na = 3.36, Ar = 3.29, H e = 0.63). Significant differentiation is seen between current and historical samples ( F ST = 0.156, P = 0.0315), and the current population exhibits extremely small N e (current N e = 2.16). There is evidence for both a recent population bottleneck and an earlier bottleneck, with population size already reasonably low by the late 19th century (historical N e = 1162.96). Individuals in the current population are related at the level of half‐ to full‐siblings between social groups, and full‐siblings or parent–offspring within a social group, suggesting that inbreeding is likely to increase in the future. The species' current reduced genetic diversity must be considered during conservation planning, particularly for expectations of likely population recovery, indicating that intensive, carefully planned management is essential.

Effects of fertilization practices on aluminum fractions and species in a wheat soil - Lei Wang; Clayton R. Butterly; Wei Tian; Herath M. S. K. Herath; Yunguan Xi; Jibing Zhang; Xingji Xiao (Journal of Soils and Sediments, 2016)

Biofortification of wheat, rice and common bean by applying foliar zinc fertilizer along with pesticides in seven countries - H. Ram; A. Rashid; W. Zhang; A. P. Duarte; N. Phattarakul; S. Simunji; M. Kalayci; R. Freitas; B. Rerkasem; R. S. Bal; K. Mahmood; E. Savasli; et al. (Plant and Soil, 2016)

High-Fat Diet Increased Renal and Hepatic Oxidative Stress Induced by Vanadium of Wistar Rat - J. P. Wang; R. Y. Cui; K. Y. Zhang; X. M. Ding; Y. H. Luo; S. P. Bai; Q. F. Zeng; Y. Xuan; Z. W. Su (Biological Trace Element Research, 2016)

Treatment of retinitis pigmentosa due to MERTK mutations by ocular subretinal injection of adeno-associated virus gene vector: results of a phase I trial - Nicola G. Ghazi; Emad B. Abboud; Sawsan R. Nowilaty; Hisham Alkuraya; Abdulrahman Alhommadi; Huimin Cai; Rui Hou; Wen-Tao Deng; Sanford L. Boye; Abdulrahman Almaghamsi; Fahad Al Saikhan; Hassan Al-Dhibi; et al. (Human Genetics, 2016)

Visual detection technique for efficient screening and isolation of Salmonella based on a novel enrichment assay using chromatography membrane - F. Tang; Y. Xiong; H. Zhang; K. Wu; Y. Xiang; J.-B. Shao; H.-W. Ai; Y.-P. Xiang; X.-L. Zheng; J.-R. Lv; H. Sun; L.-S. Bao; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Colorectal delivery and retention of PEG-Amprenavir-Bac7 nanoconjugates—proof of concept for HIV mucosal pre-exposure prophylaxis - Mahta Samizadeh; Xiaoping Zhang; Simi Gunaseelan; Antoinette G. Nelson; Matthew S. Palombo; Daniel R. Myers; Yashveer Singh; Usha Ganapathi; Zoltan Szekely; Patrick J. Sinko (Drug Delivery and Translational Research, 2016)

Thermokarst rates intensify due to climate change and forest fragmentation in an Alaskan boreal forest lowland - Mark J. Lara; Hélène Genet; Anthony D. McGuire; Eugénie S. Euskirchen; Yujin Zhang; Dana R. N. Brown; Mark T. Jorgenson; Vladimir Romanovsky; Amy Breen; William R. Bolton (Global Change Biology, 2016)
Lowland boreal forest ecosystems in Alaska are dominated by wetlands comprised of a complex mosaic of fens, collapse‐scar bogs, low shrub/scrub, and forests growing on elevated ice‐rich permafrost soils. Thermokarst has affected the lowlands of the Tanana Flats in central Alaska for centuries, as thawing permafrost collapses forests that transition to wetlands. Located within the discontinuous permafrost zone, this region has significantly warmed over the past half‐century, and much of these carbon‐rich permafrost soils are now within ~0.5 °C of thawing. Increased permafrost thaw in lowland boreal forests in response to warming may have consequences for the climate system. This study evaluates the trajectories and potential drivers of 60 years of forest change in a landscape subjected to permafrost thaw in unburned dominant forest types (paper birch and black spruce) associated with location on elevated permafrost plateau and across multiple time periods (1949, 1978, 1986, 1998, and 2009) using historical and contemporary aerial and satellite images for change detection. We developed (i) a deterministic statistical model to evaluate the potential climatic controls on forest change using gradient boosting and regression tree analysis, and (ii) a 30 × 30 m land cover map of the Tanana Flats to estimate the potential landscape‐level losses of forest area due to thermokarst from 1949 to 2009. Over the 60‐year period, we observed a nonlinear loss of birch forests and a relatively continuous gain of spruce forest associated with thermokarst and forest succession, while gradient boosting/regression tree models identify precipitation and forest fragmentation as the primary factors controlling birch and spruce forest change, respectively. Between 1950 and 2009, landscape‐level analysis estimates a transition of ~15 km² or ~7% of birch forests to wetlands, where the greatest change followed warm periods. This work highlights that the vulnerability and resilience of lowland ice‐rich permafrost ecosystems to climate changes depend on forest type.

Exogenous NO depletes Cd-induced toxicity by eliminating oxidative damage, re-establishing ATPase activity, and maintaining stress-related hormone equilibrium in white clover plants - S. L. Liu; R. J. Yang; Y. Z. Pan; M. H. Wang; Y. Zhao; M. X. Wu; J. Hu; L. L. Zhang; M. D. Ma (Environmental Science and Pollution Research, 2015)

Impacts of climate variability and extremes on global net primary production in the first decade of the 21st century - Shufen Pan; Hanqin Tian; Shree R. S. Dangal; Zhiyun Ouyang; Chaoqun Lu; Jia Yang; Bo Tao; Wei Ren; Kamaljit Banger; Qichun Yang; Bowen Zhang (Journal of Geographical Sciences, 2015)

Identification and characterization of pleiotropic and co-located resistance loci to leaf rust and stripe rust in bread wheat cultivar Sujata - Caixia Lan; Yelun Zhang; Sybil A. Herrera-Foessel; Bhoja R. Basnet; Julio Huerta-Espino; Evans S. Lagudah; Ravi P. Singh (Theoretical and Applied Genetics, 2015)

Sensilla on the Antennae and Ovipositor of the Sea Buckthorn Carpenter Moth, Holcocerus hippophaecolus Hua et al (Lepidoptera: Cossidae) - R Wang; L Zhang; L L Xu; S X Zong; Y Q Luo (Neotropical Entomology, 2015)

Molecular characterization, phylogenetic analysis and expression profiling of myoglobin and cytoglobin genes in response to heat stress in channel catfish Ictalurus punctatus - J. B. Feng; S. K. Liu; R. J. Wang; J. R. Zhang; X. L. Wang; L. Kaltenboeck; J. L. Li; Z. J. Liu (Journal of Fish Biology, 2015)
To understand the function of myoglobin (Mb) and cytoglobin (Cygb) in channel catfish Ictalurus punctatus in response to heat stress, mb and cygb genes were identified and characterized in this study. These genes were widely expressed in all the tested tissues, but strong tissue preferences were observed, with the mb gene being expressed most highly in the heart, cygb1 most highly expressed in the intestine and cygb2 most highly expressed in the brain. After heat‐stress challenge, mb and cygb genes were up‐regulated in almost all tested tissues. In general, such up‐regulation was more dramatic in the tolerant group than in the intolerant group, suggesting that higher expression of mb and cygb genes contributed to greater tolerance of I. punctatus to heat stress.

The interaction of escitalopram and R-citalopram at the human serotonin transporter investigated in the mouse - Jacob P. R. Jacobsen; Per Plenge; Benjamin D. Sachs; Alan L. Pehrson; Manuel Cajina; Yunzhi Du; Wendy Roberts; Meghan L. Rudder; Prachiti Dalvi; Taylor J. Robinson; Sharon P. O’Neill; King S. Khoo; et al. (Psychopharmacology, 2014)

Structural and Mechanical Adaptations of Right Ventricle Free Wall Myocardium to Pressure Overload - Michael R. Hill; Marc A. Simon; Daniela Valdez-Jasso; Will Zhang; Hunter C. Champion; Michael S. Sacks (Annals of Biomedical Engineering, 2014)

Enhancement of anti-bacterial and anti-tumor activities of pentacyclic triterpenes by introducing exocyclic α,β-unsaturated ketone moiety in ring A - Li R. Huang; Heng Luo; Xiao S. Yang; Lei Chen; Jian X. Zhang; Dao P. Wang; Xiao J. Hao (Medicinal Chemistry Research, 2014)

Comparison of interpolation methods for estimating spatial distribution of precipitation in Ontario, Canada - S. Wang; G. H. Huang; Q. G. Lin; Z. Li; H. Zhang; Y. R. Fan (International Journal of Climatology, 2014)
In this study, different interpolation techniques in a geographical information system ( GIS ) environment are analysed and compared for estimating the spatial distribution of precipitation in the province of Ontario, Canada. A high‐resolution regional climate modelling system [Providing Regional Climates for Impacts Studies ( PRECIS )] is used to simulate the present (1961–1990) and future (2071–2100) precipitation events for 12 meteorological stations over Ontario. The results verify that for the present case PRECIS simulates well the precipitation events when compared with observed data. The future precipitation events can be projected after the validation of PRECIS . Six interpolation methods are then used to generate spatial distribution of precipitation based on the projections of future precipitation of 12 meteorological stations; they include inverse distance weighting ( IDW ), global polynomial interpolation ( GPI ), local polynomial interpolation ( LPI ), radial basis functions ( RBF ), ordinary kriging ( OK ), and universal kriging ( UK ). Cross‐validation is applied to evaluate the accuracy of interpolation methods in terms of the root mean square error ( RMSE ). The results indicate that LPI is the optimal method with the least RMSE for interpolating the PRECIS precipitation. LPI is then used to analyse spatial variations of the average annual precipitation for the period of 2071–2100 over Ontario.

Hypothesis-independent pathway analysis implicates GABA and Acetyl-CoA metabolism in primary open-angle glaucoma and normal-pressure glaucoma - Jessica N. Cooke Bailey; Brian L. Yaspan; Louis R. Pasquale; Michael A. Hauser; Jae H. Kang; Stephanie J. Loomis; Murray Brilliant; Donald L. Budenz; William G. Christen; John Fingert; Douglas Gaasterland; Terry Gaasterland; et al. (Human Genetics, 2014)

Investigation into the atmospheric parameters retrieved from ROPP and CDAAC using GPS radio occultation measurements over the Australian area - C.-S. Wang; R. Norman; T. K. Yeh; K. Zhang; T.-P. Tseng; S. L. Choy (Australian Journal of Earth Sciences, 2014)

Eutrophication as a driver of r ‐selection traits in a freshwater fish - M. Lin; M. Chevalier; S. Lek; L. Zhang; R. E. Gozlan; J. Liu; T. Zhang; S. Ye; W. Li; Z. Li (Journal of Fish Biology, 2014)
This study tested whether eutrophication could influence life‐history traits of a cyprinid, Chanodichthys erythropterus , in 10 Chinese lakes. Using the von Bertalanffy growth model, the asymptotic length ( L ∞ ) and the growth performance index ( I GRO ) were significantly affected by eutrophication. The gonado‐somatic index ( I G ) and relative fecundity ( F R ) were significantly lower in mesotrophic lakes than in eutrophic and hypertrophic lakes. These results indicate that increasing eutrophication affects the life‐history tactics of a freshwater fish.

Importing, Caring, Breeding, Genotyping, and Phenotyping a Genetic Mouse in a Chinese University - S. T. Kuo; Q. H. Wu; B. Liu; Z. L. Xie; X. Wu; S. J. Shang; X. Y. Zhang; X. J. Kang; L. N. Liu; F. P. Zhu; Y. S. Wang; M. Q. Hu; et al. (Journal of Molecular Neuroscience, 2014)

Effect of Cocaine on Ion Channels and Glutamatergic EPSCs in Noradrenergic Locus Coeruleus Neurons - L. N. Liu; F. P. Zhu; M. Y. Song; X. J. Kang; S. J. Shang; X. Y. Zhang; H. D. Xu; S. S. Teng; B. Liu; S. T. Kuo; W. Liu; M. L. Li; et al. (Journal of Molecular Neuroscience, 2014)

The day-to-day monitoring of the 2011 severe drought in China - Er Lu; Wenyue Cai; Zhihong Jiang; Qiang Zhang; Cunjie Zhang; R. Wayne Higgins; Michael S. Halpert (Climate Dynamics, 2014)

Emergence of NDM-producing non-baumannii Acinetobacter spp. isolated from China - R. Zhang; Y.-Y. Hu; X.-F. Yang; D.-X. Gu; H.-W. Zhou; Q.-F. Hu; K. Zhao; S.-F. Yu; G.-X. Chen (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Changes in cerebral morphometry and amplitude of low-frequency fluctuations of BOLD signals during healthy aging: correlation with inhibitory control - Sien Hu; Herta H.-A. Chao; Sheng Zhang; Jaime S. Ide; Chiang-Shan R. Li (Brain Structure and Function, 2014)

Foraging Activity is Reduced in a Mouse Model of Depression - C. R. Yang; Z. G. Zhang; Y. Y. Bai; H. Fiona Zhou; L. Zhou; C. S. Ruan; F. Li; C. Q. Li; H. Y. Zheng; L. J. Shen; X. F. Zhou (Neurotoxicity Research, 2014)

Evidence for Borna disease virus infection in neuropsychiatric patients in three western China provinces - L. Zhang; M.-M. Xu; L. Zeng; S. Liu; X. Liu; X. Wang; D. Li; R.-Z. Huang; L.-B. Zhao; Q.-L. Zhan; D. Zhu; Y.-Y. Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Prostate cancer derived prostatic acid phosphatase promotes an osteoblastic response in the bone microenvironment - Sandy R. Larson; Jessica Chin; Xiaotun Zhang; Lisha G. Brown; Ilsa M. Coleman; Bryce Lakely; Martin Tenniswood; Eva Corey; Peter S. Nelson; Robert L. Vessella; Colm Morrissey (Clinical & Experimental Metastasis, 2014)

Genetic consequences of breaking migratory traditions in barnacle geese Branta leucopsis - R. M. Jonker; R. H. S. Kraus; Q. Zhang; P. van Hooft; K. Larsson; H. P. van der Jeugd; R. H. J. M. Kurvers; S. E. van Wieren; M. J. J. E. Loonen; R. P. M. A. Crooijmans; R. C. Ydenberg; M. A. M. Groenen; et al. (Molecular Ecology, 2013)
Cultural transmission of migratory traditions enables species to deal with their environment based on experiences from earlier generations. Also, it allows a more adequate and rapid response to rapidly changing environments. When individuals break with their migratory traditions, new population structures can emerge that may affect gene flow. Recently, the migratory traditions of the Barnacle Goose Branta leucopsis changed, and new populations differing in migratory distance emerged. Here, we investigate the population genetic structure of the Barnacle Goose to evaluate the consequences of altered migratory traditions. We used a set of 358 single nucleotide polymorphism ( SNP ) markers to genotype 418 individuals from breeding populations in Greenland, Spitsbergen, Russia, Sweden and the Netherlands, the latter two being newly emerged populations. We used discriminant analysis of principal components, F ST , linkage disequilibrium and a comparison of geneflow models using migrate ‐ n to show that there is significant population structure, but that relatively many pairs of SNP s are in linkage disequilibrium, suggesting recent admixture between these populations. Despite the assumed traditions of migration within populations, we also show that genetic exchange occurs between all populations. The newly established nonmigratory population in the Netherlands is characterized by high emigration into other populations, which suggests more exploratory behaviour, possibly as a result of shortened parental care. These results suggest that migratory traditions in populations are subject to change in geese and that such changes have population genetic consequences. We argue that the emergence of nonmigration probably resulted from developmental plasticity.

Isolation and molecular analysis of genes Stpk-V2 and Stpk-V3 homologous to powdery mildew resistance gene Stpk-V in a Dasypyrum villosum accession and its derivatives - Z. S. Lin; Y. L. Zhang; M. J. Wang; J. R. Li; K. Wang; X. Chen; Q. F. Xu; X. S. Zhang; X. G. Ye (Journal of Applied Genetics, 2013)

The C‐terminal cysteine of turbot Scophthalmus maximus translationally controlled tumour protein plays a key role in antioxidation and growth‐promoting functions - Z.‐X. Zhang; D.‐Y. Geng; Q. Han; S.‐D. Liang; H.‐R. Guo (Journal of Fish Biology, 2013)
The translationally controlled tumour protein (TCTP) of turbot Scophthalmus maximus ( SmTCTP ) contains only one cysteine (Cys 170 ) at the C‐terminal end. The biological role of this C‐terminal Cys 170 in the antioxidation and growth‐promoting functions of SmTCTP was examined by site‐directed mutation of C170A (Cys 170 →Ala 170 ). It was found that C170A mutation not only obviously decreased the antioxidation capacity of the mutant‐ smtctp ‐transformed bacteria exposed to 0·22 mM hydrogen peroxide, but also significantly interrupted the normal growth and survival of the mutant‐ smtctp ‐transformed bacteria and flounder Paralichthys olivaceus gill ( FG ) cells, indicating a key role played by Cys 170 in the antioxidation and growth‐promoting functions of SmTCTP . This study also suggested that the self‐dimerization or dimerization with other interacting proteins is critical to the growth‐promoting function of SmTCTP .

Environmental impact and cost assessment of incineration and ethanol production as municipal solid waste management strategies - Mir Abbas Bozorgirad; Hao Zhang; Karl R. Haapala; Ganti S. Murthy (The International Journal of Life Cycle Assessment, 2013)

Soluble interleukin‐1 receptor, a potential negative regulator of orange‐spotted grouper Epinephelus coioides interleukin‐1 system - D. Q. Lu; M. Yao; S. B. Yi; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2013)
In this study, the cDNA sequence encoding interleukin‐1 ( Il ‐1) receptor‐like protein of orange‐spotted grouper Epinephelus coioides was obtained. The newly identified sequence was named soluble type I Il ‐1 receptor ( sIl‐1rI ) owing to its structural composition, which had two Ig‐like domains, lack of transmembrane region and the Toll/interleukin‐1 receptor ( TIR ) domain, similar to the brown rat Rattus norvegicus soluble Il‐1rI . In addition, sequence comparison and phylogenetic analysis indicated that E. coioides sequence had a closer relationship with Il‐1rI than Il‐1rII . Real‐time PCR revealed that sil‐1rI mRNA expression presented a process of decrease, restoration and increase in Cryptocaryon irritans ‐infected E. coioides . The negative correlation between Il ‐1β and sil‐1rI mRNA in C. irritans ‐infected head‐kidney implied the potential negative regulatory role of sil‐1rI in E. coioides Il ‐1 system. The leucocytes incubated with lipopolysaccharide or polyriboinosinic polyribocytidylic acid exhibited different expression profiles of sil‐1rI . Recombinant Il ‐1β ( rIl ‐1β) protein was capable of inducing sil‐1rI mRNA under the concentration of 100 ng ml −1 , suggesting that high dosage or excess Il ‐1β would stimulate the expression of sil‐1rI to maintain the homoeostasis of E. coioides Il ‐1 system. For the first time, the role of teleost Il‐1rI in parasite infection has been identified, and soluble Il‐1r was found in fish.

Radiation hybrid QTL mapping of Tdes2 involved in the first meiotic division of wheat - F. M. Bassi; A. Kumar; Q. Zhang; E. Paux; E. Huttner; A. Kilian; R. Dizon; C. Feuillet; S. S. Xu; S. F. Kianian (Theoretical and Applied Genetics, 2013)

Molecular investigation of bacterial communities on the inner and outer surfaces of peripheral venous catheters - L. Zhang; M. Morrison; G. R. Nimmo; K. S. Sriprakash; S. Mondot; J. R. Gowardman; N. George; N. Marsh; C. M. Rickard (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Recognition of shelterbelt continuity using remote sensing and waveform recognition - R. X. Deng; Y. Li; W. J. Wang; S. W. Zhang (Agroforestry Systems, 2013)

Implications of CMIP3 model biases and uncertainties for climate projections in the western tropical Pacific - Jaclyn N. Brown; Alex Sen Gupta; Josephine R. Brown; Les C. Muir; James S. Risbey; Penny Whetton; Xuebin Zhang; Alexandre Ganachaud; Brad Murphy; Susan E. Wijffels (Climatic Change, 2013)

Three genetic systems controlling growth, development and productivity of rice (Oryza sativa L.): a reevaluation of the ‘Green Revolution’ - Fan Zhang; Yun-Zhu Jiang; Si-Bin Yu; J. Ali; A. H. Paterson; G. S. Khush; Jian-Long Xu; Yong-Ming Gao; Bin-Ying Fu; R. Lafitte; Zhi-Kang Li (Theoretical and Applied Genetics, 2013)

Bacterial TIR-containing proteins and host innate immune system evasion - Rohini R. Rana; Minghao Zhang; Abigail M. Spear; Helen S. Atkins; Bernadette Byrne (Medical Microbiology and Immunology, 2013)

Fine mapping and characterization of BPH27, a brown planthopper resistance gene from wild rice (Oryza rufipogon Griff.) - D. Huang; Y. Qiu; Y. Zhang; F. Huang; J. Meng; S. Wei; R. Li; B. Chen (Theoretical and Applied Genetics, 2013)

Smoking, variation in N-acetyltransferase 1 (NAT1) and 2 (NAT2), and risk of non-Hodgkin lymphoma: a pooled analysis within the InterLymph consortium - Todd M. Gibson; Karin E. Smedby; Christine F. Skibola; David W. Hein; Susan L. Slager; Silvia de Sanjosé; Claire M. Vajdic; Yawei Zhang; Brian C.-H. Chiu; Sophia S. Wang; Henrik Hjalgrim; Alexandra Nieters; et al. (Cancer Causes & Control, 2013)

Biofortification of wheat with zinc through zinc fertilization in seven countries - C. Q. Zou; Y. Q. Zhang; A. Rashid; H. Ram; E. Savasli; R. Z. Arisoy; I. Ortiz-Monasterio; S. Simunji; Z. H. Wang; V. Sohu; M. Hassan; Y. Kaya; et al. (Plant and Soil, 2012)

A 5′UTR SNP of GHRHR locus is associated with body weight and average daily gain in Chinese cattle - C. F. Zhang; H. Chen; Z. Y. Zhang; L. Z. Zhang; D. Y. Yang; Y. J. Qu; L. S. Hua; B. Zhang; S. R. Hu (Molecular Biology Reports, 2012)

An SNP in the MyoD1 Gene Intron 2 Associated with Growth and Carcass Traits in Three Duck Populations - Y. Wu; J. S. Pi; A. L. Pan; Y. J. Pu; J. P. Du; J. Shen; Z. H. Liang; J. R. Zhang (Biochemical Genetics, 2012)

The polymorphism analysis of CD169 and CD163 related with the risk of porcine reproductive and respiratory syndrome virus (PRRSV) infection - Y. W. Ren; Y. Y. Zhang; N. A. Affara; C. A. Sargent; L. G. Yang; J. L. Zhao; L. R. Fang; J. J. Wu; R. Fang; Q. Tong; J. Xiao; J. L. Li; et al. (Molecular Biology Reports, 2012)

Isolation and partial characterization of a new reovirus in the Chinese mitten crab, Eriocheir sinensis H Milne Edwards - S Zhang; J‐R Bonami (Journal of Fish Diseases, 2012)
A second type of freshwater crab reovirus has been isolated from Chinese mitten crab, Eriocheir sinensis H. Milne Edwards, in China; we named it E. sinensis reovirus ( Es RV816). The negatively stained virion is a non‐enveloped icosahedral particle, 60 ± 5 nm in diameter. Its genome is composed of 10 dsRNA linear pieces exhibiting an electrophoretic pattern of 5/3/2. The largest segment (RNA‐1) was cloned and sequenced. The deduced amino acid sequence, corresponding to the RdRp of the virus, showed 26% identity with the RdRp of Operophtera brumata (L.) cypovirus 19 in the genus Cypovirus and 24% identity with RdRp of Nilaparvata lugens (Stal) reovirus in the genus Fijivirus . On the basis of its ultrastructure and physicochemical properties, this virus is quite different from other crab reoviruses, and particularly with another freshwater crab reovirus Es RV905, recently classified in a new genus Cardoreovirus . This virus ( Es RV816) possesses all the characters of the members of the reoviridae family and could represent a new genus.

Characterization and molecular mapping of Yr52 for high-temperature adult-plant resistance to stripe rust in spring wheat germplasm PI 183527 - R. S. Ren; M. N. Wang; X. M. Chen; Z. J. Zhang (Theoretical and Applied Genetics, 2012)

Germplasm evaluation and transfer of Verticillium wilt resistance from Pima (Gossypium barbadense) to Upland cotton (G. hirsutum) - Jinfa Zhang; S. Sanogo; R. Flynn; Jit B. Baral; S. Bajaj; S. E. Hughs; Richard G. Percy (Euphytica, 2012)

Negative Effect of High Calcium Levels on Schwann Cell Survival - J.-G. Yan; M. Agresti; L.-L. Zhang; H. S. Matloub; J. R. Sanger (Neurophysiology, 2012)

Drug–Drug Interaction Potential of Marketed Oncology Drugs: In Vitro Assessment of Time-Dependent Cytochrome P450 Inhibition, Reactive Metabolite Formation and Drug–Drug Interaction Prediction - Jane R. Kenny; Sophie Mukadam; Chenghong Zhang; Suzanne Tay; Carol Collins; Aleksandra Galetin; S. Cyrus Khojasteh (Pharmaceutical Research, 2012)

Identification and expression analysis of major histocompatibility complex IIB gene in orange‐spotted grouper Epinephelus coioides - D. Q. Lu; S. B. Yi; M. Yao; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2012)
In this study, complementary DNA (cDNA) and DNA sequences of major histocompatibility complex (MHC) class IIB genes ( mhcIIB ) were cloned from orange‐spotted grouper Epinephelus coioides . The gene structure of E. coioides mhcIIB consists of five exons and four introns, and its deduced amino acid sequence length is 249 amino acids, including a signal peptide, a peptide‐binding region, an IGC1 domain, a transmembrane region and a cytoplasmic tail. A phylogenetic study showed that E. coioides mhcIIB shared 32·0–79·1% identity with those of other teleosts and mammals. Real‐time reverse transcriptase (RT)‐PCR was performed to detect the class IIB gene expression in eight different tissues. To characterize the relationship between E. coioides mhcIIB gene and pathogens, in vivo and in vitro studies were performed. Challenge of Cryptocaryon irritans revealed that class IIB genes were down‐regulated after 24 and 48 h of challenge, and their expression was later restored at 72 h. Stimulation of isolated E. coioides leukocytes with lipopolysaccharide (LPS) and polyinosinic:polycytidylic acid (PolyI:C) significantly increased peripheral blood and spleen mhcIIB expression, while head kidney mhcIIB expression remained constant.

Erratum to: Production of transgenic tropical maize with cryIAb and cryIAc genes via microprojectile bombardment of immature embryos - N. Bohorova; W. Zhang; P. Julstrom; S. McLean; B. Luna; R. M. Brito; L. Diaz; M. E. Ramos; P. Estanol; M. Pacheco; M. Salgado; D. Hoisington (Theoretical and Applied Genetics, 2012)

Molecular cloning, characterization expression of P450c17-I and P450c17-II and their functions analysis during the reproductive cycle in males of barfin flounder (Verasper moseri) - Guo X. Jin; Hai S. Wen; Feng He; Ji F. Li; Cai F. Chen; Jia R. Zhang; Xiao Y. Chen; Bao Shi; Dan Shi; Yan P. Yang; Bao X. Qi; Na Li (Fish Physiology and Biochemistry, 2012)

Russian wheat aphids ( Diuraphis noxia ) in China: native range expansion or recent introduction? - B. ZHANG; O. R. EDWARDS; L. KANG; S. J. FULLER (Molecular Ecology, 2012)
In this study, we explore the population genetics of the Russian wheat aphid (RWA) ( Diuraphis noxia ), one of the world’s most invasive agricultural pests, in north‐western China. We have analysed the data of 10 microsatellite loci and mitochondrial sequences from 27 populations sampled over 2 years in China. The results confirm that the RWAs are holocyclic in China with high genetic diversity indicating widespread sexual reproduction. Distinct differences in microsatellite genetic diversity and distribution revealed clear geographic isolation between RWA populations in northern and southern Xinjiang, China, with gene flow interrupted across extensive desert regions. Despite frequent grain transportation from north to south in this region, little evidence for RWA translocation as a result of human agricultural activities was found. Consequently, frequent gene flow among northern populations most likely resulted from natural dispersal, potentially facilitated by wind currents. We also found evidence for the long‐term existence and expansion of RWAs in China, despite local opinion that it is an exotic species only present in China since 1975. Our estimated date of RWA expansion throughout China coincides with the debut of wheat domestication and cultivation practices in western Asia in the Holocene. We conclude that western China represents the limit of the far eastern native range of this species. This study is the most comprehensive molecular genetic investigation of the RWA in its native range undertaken to date and provides valuable insights into the history of the association of this aphid with domesticated cereals and wild grasses.

Water sources of urban trees in the Los Angeles metropolitan area - Neeta S. Bijoor; Heather R. McCarthy; Dachun Zhang; Diane E. Pataki (Urban Ecosystems, 2012)

Case report: a p.C618S RET proto-oncogene germline mutation in a large Chinese pedigree with familial medullary thyroid carcinoma - X.-P. Qi; R.-B. Ying; J.-M. Ma; W.-T. Liu; Z.-F. Du; J. Fei; C.-P. Yang; Q.-Z. Song; H.-Y. Jin; Z.-G. Chen; J.-S. Han; J.-Q. Wang; et al. (Familial Cancer, 2012)

Biomimetic tubular nanofiber mesh and platelet rich plasma-mediated delivery of BMP-7 for large bone defect regeneration - A. Berner; J. D. Boerckel; S. Saifzadeh; R. Steck; J. Ren; C. Vaquette; J. Qiyi Zhang; M. Nerlich; R. E. Guldberg; D. W. Hutmacher; M. A. Woodruff (Cell and Tissue Research, 2012)

Molecular diversity of bacteria in Yunnan yellow cattle (Bos taurs) from Nujiang region, China - J. Leng; Y. M. Cheng; C. Y. Zhang; R. J. Zhu; S. L. Yang; X. Gou; W. D. Deng; H. M. Mao (Molecular Biology Reports, 2012)

Consolidated Pretreatment and Hydrolysis of Plant Biomass Expressing Cell Wall Degrading Enzymes - Dongcheng Zhang; Amy L. VanFossen; Ryan M. Pagano; Jeremy S. Johnson; Matthew H. Parker; Shihao Pan; Benjamin N. Gray; Elaina Hancock; Daniel J. Hagen; Héctor A. Lucero; Binzhang Shen; Philip A. Lessard; et al. (BioEnergy Research, 2011)

Heterogeneity of primary glioblastoma cells in the expression of caspase-8 and the response to TRAIL-induced apoptosis - Ling Qi; Anita C. Bellail; Michael R. Rossi; Zhaobin Zhang; Hui Pang; Stephen Hunter; Cynthia Cohen; Carlos S. Moreno; Jeffrey J. Olson; Shibo Li; Chunhai Hao (Apoptosis, 2011)

Field testing of erodibility of two landslide dams triggered by the 12 May Wenchuan earthquake - D. S. Chang; L. M. Zhang; Y. Xu; R. Q. Huang (Landslides, 2011)

Isolation, sequence analysis, and characterization of androgen receptor in Southern catfish, Silurus meridionalis - B. F. Huang; Y. L. Sun; F. R. Wu; Z. H. Liu; Z. J. Wang; L. F. Luo; Y. G. Zhang; D. S. Wang (Fish Physiology and Biochemistry, 2011)

Comparative analysis of inactivated-state block of N-type (Cav2.2) calcium channels - Timothy A. Vortherms; Andrew M. Swensen; Wende Niforatos; James T. Limberis; Torben R. Neelands; Richard S. Janis; Rama Thimmapaya; Diana L. Donnelly-Roberts; Marian T. Namovic; Di Zhang; C. Brent Putman; Ruth L. Martin; et al. (Inflammation Research, 2011)

Infratentorial Strokes for Posterior Circulation Folks: Clinical Correlations for Current Translational Therapeutics - Tim Lekic; Paul R. Krafft; Jacqueline S. Coats; Andre Obenaus; Jiping Tang; John H. Zhang (Translational Stroke Research, 2011)

A novel Robertsonian translocation event leads to transfer of a stem rust resistance gene (Sr52) effective against race Ug99 from Dasypyrum villosum into bread wheat - L. L. Qi; M. O. Pumphrey; Bernd Friebe; P. Zhang; C. Qian; R. L. Bowden; M. N. Rouse; Y. Jin; B. S. Gill (Theoretical and Applied Genetics, 2011)

Human Pathogenic Fungi in China—Emerging Trends from Ongoing National Survey for 1986, 1996, and 2006 - S. X. Wu; N. R. Guo; X. F. Li; W. Q. Liao; M. Chen; Q. Q. Zhang; C. Y. Li; R. Y. Li; G. S. Bulmer; D. M. Li; L. Y. Xi; S. Lu; et al. (Mycopathologia, 2011)

Quantitative trait loci for temperature-sensitive resistance to Puccinia striiformis f. sp. tritici in wheat cultivar Flinor - J. Feng; L. L. Zuo; Z. Y. Zhang; R. M. Lin; Y. Y. Cao; S. C. Xu (Euphytica, 2011)

A new long terminal repeat (LTR) sequence allows to identify J genome from JS and St genomes of Thinopyrum intermedium - Z. X. Tang; Z. J. Yang; S. L. Fu; M. Y. Yang; G. R. Li; H. Q. Zhang; F. Q. Tan; Zhenglong Ren (Journal of Applied Genetics, 2011)

Initial results from Phase 2 of the international urban energy balance model comparison - C. S. B. Grimmond; M. Blackett; M. J. Best; J.‐J. Baik; S. E. Belcher; J. Beringer; S. I. Bohnenstengel; I. Calmet; F. Chen; A. Coutts; A. Dandou; K. Fortuniak; et al. (International Journal of Climatology, 2011)
Urban land surface schemes have been developed to model the distinct features of the urban surface and the associated energy exchange processes. These models have been developed for a range of purposes and make different assumptions related to the inclusion and representation of the relevant processes. Here, the first results of Phase 2 from an international comparison project to evaluate 32 urban land surface schemes are presented. This is the first large‐scale systematic evaluation of these models. In four stages, participants were given increasingly detailed information about an urban site for which urban fluxes were directly observed. At each stage, each group returned their models' calculated surface energy balance fluxes. Wide variations are evident in the performance of the models for individual fluxes. No individual model performs best for all fluxes. Providing additional information about the surface generally results in better performance. However, there is clear evidence that poor choice of parameter values can cause a large drop in performance for models that otherwise perform well. As many models do not perform well across all fluxes, there is need for caution in their application, and users should be aware of the implications for applications and decision making. Copyright © 2010 Royal Meteorological Society

Neuromelanin Activates Microglia and Induces Degeneration of Dopaminergic Neurons: Implications for Progression of Parkinson’s Disease - Wei Zhang; Kester Phillips; Albert R. Wielgus; Jie Liu; Alberto Albertini; Fabio A. Zucca; Rudolph Faust; Steven Y. Qian; David S. Miller; Colin F. Chignell; Belinda Wilson; Vernice Jackson-Lewis; et al. (Neurotoxicity Research, 2011)

Characterization of the GHR gene genetic variation in Chinese indigenous goat breeds - W. L. Bai; C. Y. Zhou; Y. Ren; R. H. Yin; W. Q. Jiang; S. J. Zhao; S. C. Zhang; B. L. Zhang; G. B. Luo; Z. H. Zhao (Molecular Biology Reports, 2011)

MyoD control of SKIP expression during pig skeletal muscle development - Q. Xiong; J. Chai; P. P. Zhang; J. Wu; S. W. Jiang; R. Zheng; C. Y. Deng (Molecular Biology Reports, 2011)

Thromboxane-prostanoid receptor expression and antagonism in dextran-sodium sulfate-induced colitis - Patsy R. Carter; Robert M. McElhatten; Songlin Zhang; William S. Wright; Norman R. Harris (Inflammation Research, 2011)

Expression of GDF-9, BMP-15 and their receptors in mammalian ovary follicles - R. Z. Sun; L. Lei; L. Cheng; Z. F. Jin; S. J. Zu; Z. Y. Shan; Z. D. Wang; J. X. Zhang; Z. H. Liu (Journal of Molecular Histology, 2010)

Cloning and expression of P450c17-I (17α-hydroxylase/17,20-lyase) in brain and ovary during gonad development in Cynoglossus semilaevis - Cai F. Chen; Hai S. Wen; Zhao P. Wang; Feng He; Jia R. Zhang; Xiao Y. Chen; Guo X. Jin; Bao Shi; Dan Shi; Yan P. Yang; Ji F. Li; Bao X. Qi; et al. (Fish Physiology and Biochemistry, 2010)

Viral and Mycoplasma pneumoniae community-acquired pneumonia and novel clinical outcome evaluation in ambulatory adult patients in China - B. Cao; L.-L. Ren; F. Zhao; R. Gonzalez; S.-F. Song; L. Bai; Y. D. Yin; Y.-Y. Zhang; Y.-M. Liu; P. Guo; J.-Z. Zhang; J.-W. Wang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Development of rapid immunoassays for the detection of ractopamine in swine urine - X. Li; G. Zhang; R. Deng; Y. Yang; Q. Liu; Z. Xiao; J. Yang; G. Xing; D. Zhao; S. Cai (Food Additives & Contaminants: Part A, 2010)

The rag locus of Porphyromonas gingivalis might arise from Bacteroides via horizontal gene transfer - Z. Su; F. Kong; S. Wang; J. Chen; R. Yin; C. Zhou; Y. Zhang; Z. He; Y. Shi; Y. Xue; X. Shi; L. Lu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Transformation of an Agulhas eddy near the continental slope - S. Baker-Yeboah; G. R. Flierl; G. G. Sutyrin; Y. Zhang (Ocean Science, 2010)
The transformation of Agulhas eddies near the continental slope of southern Africa and their subsequent self-propagation are analyzed in both observational data and numerical simulations. Self-propagation results from a net dipole moment of a generalized heton structure consisting of a surface-intensified anticyclonic eddy and deep cyclonic pattern. Such Agulhas vortical structures can form near the retroflection region and further north along the western coast of southern Africa. We analyze nonlinear topographic wave generation, vortex deformations, and filament production as an important part in water mass exchange. Self-propagating structures provide a conduit for exchange between the deep ocean and shelf regions in the Benguela upwelling system.

Effects of Erysiphe pisi on protein profiles and ribulose-1,5-bisphosphate carboxylase content in resistant and susceptible pea (Pisum sativum × Pisum fulvum) plants - S. F. Hwang; X. R. Zhang; S. E. Strelkov; K. F. Chang; G. D. Turnbull; J. Vidmar (Journal of Plant Diseases and Protection, 2010)

Preliminary evaluation on the use of homing pigeons as a biomonitor in urban areas - W. X. Liu; X. Ling; R. S. Halbrook; D. Martineau; H. Dou; X. Liu; G. Zhang; S. Tao (Ecotoxicology, 2010)

Evidence for a new allele at the SERCA1 locus affecting pork meat quality in part through the imbalance of Ca2+ homeostasis - J. Chai; Q. Xiong; P. P. Zhang; Y. Y. Shang; R. Zheng; J. Peng; S. W. Jiang (Molecular Biology Reports, 2010)

Molecular characterization of an earliest cacao (Theobroma cacao L.) collection from Upper Amazon using microsatellite DNA markers - Dapeng Zhang; Michel Boccara; Lambert Motilal; Sue Mischke; Elizabeth S. Johnson; David R. Butler; Bryan Bailey; Lyndel Meinhardt (Tree Genetics & Genomes, 2009)

Intercomparison, interpretation, and assessment of spring phenology in North America estimated from remote sensing for 1982–2006 - MICHAEL A. WHITE; KIRSTEN M. De BEURS; KAMEL DIDAN; DAVID W. INOUYE; ANDREW D. RICHARDSON; OLAF P. JENSEN; JOHN O'KEEFE; GONG ZHANG; RAMAKRISHNA R. NEMANI; WILLEM J. D. Van LEEUWEN; JESSLYN F. BROWN; ALLARD De WIT; et al. (Global Change Biology, 2009)
Shifts in the timing of spring phenology are a central feature of global change research. Long‐term observations of plant phenology have been used to track vegetation responses to climate variability but are often limited to particular species and locations and may not represent synoptic patterns. Satellite remote sensing is instead used for continental to global monitoring. Although numerous methods exist to extract phenological timing, in particular start‐of‐spring (SOS), from time series of reflectance data, a comprehensive intercomparison and interpretation of SOS methods has not been conducted. Here, we assess 10 SOS methods for North America between 1982 and 2006. The techniques include consistent inputs from the 8 km Global Inventory Modeling and Mapping Studies Advanced Very High Resolution Radiometer NDVIg dataset, independent data for snow cover, soil thaw, lake ice dynamics, spring streamflow timing, over 16 000 individual measurements of ground‐based phenology, and two temperature‐driven models of spring phenology. Compared with an ensemble of the 10 SOS methods, we found that individual methods differed in average day‐of‐year estimates by ±60 days and in standard deviation by ±20 days. The ability of the satellite methods to retrieve SOS estimates was highest in northern latitudes and lowest in arid, tropical, and Mediterranean ecoregions. The ordinal rank of SOS methods varied geographically, as did the relationships between SOS estimates and the cryospheric/hydrologic metrics. Compared with ground observations, SOS estimates were more related to the first leaf and first flowers expanding phenological stages. We found no evidence for time trends in spring arrival from ground‐ or model‐based data; using an ensemble estimate from two methods that were more closely related to ground observations than other methods, SOS trends could be detected for only 12% of North America and were divided between trends towards both earlier and later spring.

Characterization of individual airborne particles in Taiyuan City, China - R. K. Xie; H. M. Seip; L. Liu; D. S. Zhang (Air Quality, Atmosphere & Health, 2009)

Integration of Satellite Imagery and Forest Inventory in Mapping Dominant and Associated Species at a Regional Scale - Yangjian Zhang; Hong S. He; William D. Dijak; Jian Yang; Stephen R. Shifley; Brian J. Palik (Environmental Management, 2009)

aPCR-SSCP and DNA sequencing detecting two silent SNPs at KAP8.1 gene in the cashmere goat - M. Zhao; H. Chen; X. Wang; H. Yu; M. Wang; J. Wang; X. Y. Lan; C. F. Zhang; L. Z. Zhang; Y. K. Guo; B. Zhang; S. R. Hu (Molecular Biology Reports, 2009)

Physiological response of bovine subcommissural organ to endothelin 1 and bradykinin - S. Schöniger; T. Caprile; C. R. Yulis; Q. Zhang; E. M. Rodríguez; F. Nürnberger (Cell and Tissue Research, 2009)

Biomass measurements and relationships with Landsat‐7/ETM+ and JERS‐1/SAR data over Canada's western sub‐arctic and low arctic - Wenjun Chen; D. Blain; Junhua Li; K. Keohler; R. Fraser; Yu Zhang; S. Leblanc; I. Olthof; Jixin Wang; M. McGovern (International Journal of Remote Sensing, 2009)

Effect of nitrogen form on the rhizosphere dynamics and uptake of cadmium and zinc by the hyperaccumulator Thlaspi caerulescens - H. L. Xie; R. F. Jiang; F. S. Zhang; S. P. McGrath; F. J. Zhao (Plant and Soil, 2009)

Physiological and biochemical responses of in vitro Fusarium oxysporum f.sp. niveum to benzoic acid - H. -S. Wu; Y. Wang; C. -Y. Zhang; M. Gu; Y. -X. Liu; G. Chen; J. -H. Wang; Z. Tang; Z. -S. Mao; Q. -R. Shen (Folia Microbiologica, 2009)

Use of gene probes to assess the impact and effectiveness of aerobic in situ bioremediation of TCE - Terry C. Hazen; Romy Chakraborty; James M. Fleming; Ingrid R. Gregory; John P. Bowman; Luis Jimenez; Dai Zhang; Susan M. Pfiffner; Fred J. Brockman; Gary S. Sayler (Archives of Microbiology, 2009)

Primary molecular features of self-incompatible and self-compatible F1 seedling from apricot (Prunus armeniaca L.) Katy × Xinshiji - J. R. Feng; X. S. Chen; Z. H. Yuan; L. J. Zhang; Z. J. Ci; X. L. Liu; C. Y. Zhang (Molecular Biology Reports, 2009)

QTL mapping for grain filling rate and yield-related traits in RILs of the Chinese winter wheat population Heshangmai × Yu8679 - R. X. Wang; L. Hai; X. Y. Zhang; G. X. You; C. S. Yan; S. H. Xiao (Theoretical and Applied Genetics, 2009)

Dancing to different tunes: heterospecific deciphering of the honeybee waggle dance - K. Tan; M. X. Yang; S. E. Radloff; H. R. Hepburn; Z. Y. Zhang; L. J. Luo; H. Li (The Science of Nature, 2008)

Quick detection of Leifsonia xyli subsp. xyli by PCR and nucleotide sequence analysis of PCR amplicons from Chinese Leifsonia xyli subsp. xyli isolates - S. -J. Gao; Y. -B. Pan; R. -K. Chen; P. -H. Chen; H. Zhang; L. -P. Xu (Sugar Tech, 2008)

Molecular characterization of the encoding regions and tissue expression analyses for three novel porcine genes––HNRPA1, YIPF5 and UB2D2 - G. Y. Liu; S. Z. Gao; C. R. Ge; X. Zhang (Molecular Biology Reports, 2008)

Effects of streptozotocin-induced diabetes on connexin43 mRNA and protein expression in ventricular muscle - F. C. Howarth; N. J. Chandler; S. Kharche; J. O. Tellez; I. D. Greener; T. T. Yamanushi; R. Billeter; M. R. Boyett; H. Zhang; H. Dobrzynski (Molecular and Cellular Biochemistry, 2008)

Effects of high glucose plus high insulin on proliferation and apoptosis of mouse endothelial progenitor cells - W. Zhang; X. Wang; H. Jin; R. Qian; G. Zhang; S. Chen; R. Hu (Inflammation Research, 2008)

Identification of quantitative trait loci for seed storability in rice (Oryza sativa L.) - Y. Xue; S. Q. Zhang; Q. H. Yao; R. H. Peng; A. S. Xiong; X. Li; W. M. Zhu; Y. Y. Zhu; D. S. Zha (Euphytica, 2008)

Detection of concurrent infection with multiple dengue virus serotypes in Thai children by ELISA and nested RT-PCR assay - P. Chinnawirotpisan; M. P. Mammen; A. Nisalak; B. Thaisomboonsuk; S. Narupiti; V. Thirawuth; R. Putnak; Chunlin Zhang (Archives of Virology, 2008)

Genetic mapping and QTL analysis of fruit and flower related traits in cucumber (Cucumis sativus L.) using recombinant inbred lines - X. J. Yuan; J. S. Pan; R. Cai; Y. Guan; L. Z. Liu; W. W. Zhang; Z. Li; H. L. He; C. Zhang; L. T. Si; L. H. Zhu (Euphytica, 2008)

Power output and columbic efficiencies from biofilms of Geobacter sulfurreducens comparable to mixed community microbial fuel cells - K. P. Nevin; H. Richter; S. F. Covalla; J. P. Johnson; T. L. Woodard; A. L. Orloff; H. Jia; M. Zhang; D. R. Lovley (Environmental Microbiology, 2008)
Summary It has been previously noted that mixed communities typically produce more power in microbial fuel cells than pure cultures. If true, this has important implications for the design of microbial fuel cells and for studying the process of electron transfer on anode biofilms. To further evaluate this, Geobacter sulfurreducens was grown with acetate as fuel in a continuous flow ‘ministack’ system in which the carbon cloth anode and cathode were positioned in close proximity, and the cation‐selective membrane surface area was maximized in order to overcome some of the electrochemical limitations that were inherent in fuel cells previously employed for the study of pure cultures. Reducing the size of the anode in order to eliminate cathode limitation resulted in maximum current and power densities per m 2 of anode surface of 4.56 A m −2 and 1.88 W m −2 respectively. Electron recovery as current from acetate oxidation was c . 100% when oxygen diffusion into the system was minimized. This performance is comparable to the highest levels previously reported for mixed communities in similar microbial fuel cells and slightly higher than the power output of an anaerobic sludge inoculum in the same ministack system. Minimizing the volume of the anode chamber yielded a volumetric power density of 2.15 kW m −3 , which is the highest power density per volume yet reported for a microbial fuel cell. Geobacter sulfurreducens formed relatively uniform biofilms 3–18 μm thick on the carbon cloth anodes. When graphite sticks served as the anode, the current density (3.10 A m −2 ) was somewhat less than with the carbon cloth anodes, but the biofilms were thicker ( c . 50 μm) with a more complex pillar and channel structure. These results suggest that the previously observed disparity in power production in pure and mixed culture microbial fuel cell systems can be attributed more to differences in the fuel cell designs than to any inherent superior capability of mixed cultures to produce more power than pure cultures.

Mapping quantitative trait loci for oil, starch, and protein concentrations in grain with high-oil maize by SSR markers - J. Zhang; X. Q. Lu; X. F. Song; J. B. Yan; T. M. Song; J. R. Dai; T. Rocheford; J. S. Li (Euphytica, 2008)

Contaminant Concentrations and Histopathological Effects in Sacramento Splittail (Pogonichthys macrolepidotus) - Ben K. Greenfield; Swee J. Teh; John R. M. Ross; Jennifer Hunt; GuoHua Zhang; Jay A. Davis; Gary Ichikawa; David Crane; Silas S. O. Hung; DongFang Deng; Foo-Ching Teh; Peter G. Green (Archives of Environmental Contamination and Toxicology, 2008)

Establishment of genetic transformation system and obtaining transgenic sugarcane (var. badila) transformed with RS gene - L. -P. Xu; Y. -X. Que; J. -S. Xu; S. -R. Fang; M. -Q Zhang; Y. -Q. Chen; R. -K. Chen (Sugar Tech, 2008)

Competitive interaction between two functional S-haplotypes confer self-compatibility on tetraploid Chinese cherry (Prunus pseudocerasus Lindl. CV. Nanjing Chuisi) - S.-X. Huang; H.-Q. Wu; Y.-R. Li; J. Wu; S.-J. Zhang; W. Heng; S.-L. Zhang (Plant Cell Reports, 2008)

Isolation, sequence identification and tissue expression distribution of three novel porcine genes—RAB14, S35A3 and ITM2A - G. Y. Liu; C. R. Ge; X. Zhang; S. Z. Gao (Molecular Biology Reports, 2008)

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

A Numerical Model Simulating the Remediation of Hydrocarbon-Impacted Soils Using Low-Temperature Oxidation - M. Kashir; K. Zhang; G. Achari; R. G. Moore; S. A. Mehta; M. G. Ursenbach (Environmental Modeling & Assessment, 2008)

Variation of photosynthetic capacity with leaf age in an alpine orchid, Cypripedium flavum - S. B. Zhang; H. Hu; Z. R. Li (Acta Physiologiae Plantarum, 2008)

The complete nucleotide sequence of a novel Tobamovirus, Rehmannia mosaic virus - Z. C. Zhang; C. Y. Lei; L. F. Zhang; X. X. Yang; R. Chen; D. S. Zhang (Archives of Virology, 2008)

Reproductive performance of Matou goat under sub-tropical monsoonal climate of Central China - M. Moaeen-ud-Din; L. G. Yang; S. L. Chen; Z. R. Zhang; J. Z. Xiao; Q. Y. Wen; M. Dai (Tropical Animal Health and Production, 2008)

Using molecular markers to identify two major loci controlling carotenoid contents in maize grain - Subhash Chander; Y. Q. Guo; X. H. Yang; J. Zhang; X. Q. Lu; J. B. Yan; T. M. Song; T. R. Rocheford; J. S. Li (Theoretical and Applied Genetics, 2008)

Transferring water from irrigation to higher valued uses: a case study of the Zhanghe irrigation system in China - R. Loeve; B. Dong; L. Hong; C. D. Chen; S. Zhang; R. Barker (Paddy and Water Environment, 2007)

Improving Toxicity of Bacillus thuringiensis Strain Contains the cry8Ca Gene Specific to Anomala corpulenta Larvae - C. Shu; R. Liu; R. Wang; J. Zhang; S. Feng; D. Huang; F. Song (Current Microbiology, 2007)

Genetic variation and phylogenetic analysis of 22 French isolates of equine arteritis virus - J. Zhang; F. Miszczak; S. Pronost; C. Fortier; U. B. R. Balasuriya; S. Zientara; G. Fortier; P. J. Timoney (Archives of Virology, 2007)

Climate simulations for 1880–2003 with GISS modelE - J. Hansen; M. Sato; R. Ruedy; P. Kharecha; A. Lacis; R. Miller; L. Nazarenko; K. Lo; G. A. Schmidt; G. Russell; I. Aleinov; S. Bauer; et al. (Climate Dynamics, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Origin and evolution of topaz-bearing granites from the Nanling Range, South China: a geochemical and Sr–Nd–Hf isotopic study - J.-H. Yu; S. Y. O’Reilly; L. Zhao; W. L. Griffin; M. Zhang; X. Zhou; S.-Y. Jiang; L.-J. Wang; R.-C. Wang (Mineralogy and Petrology, 2007)

Chronic oxidative stress as a mechanism for glucose toxicity of the beta cell in Type 2 diabetes - R. Paul Robertson; Huarong Zhou; Tao Zhang; Jamie S. Harmon (Cell Biochemistry and Biophysics, 2007)

Bee-hawking by the wasp, Vespa velutina, on the honeybees Apis cerana and A. mellifera - K. Tan; S. E. Radloff; J. J. Li; H. R. Hepburn; M. X. Yang; L. J. Zhang; P. Neumann (The Science of Nature, 2007)

Simulation of vertical wind profile under neutral conditions - T. X. Yue; W. Wang; Q. Yu; Z. L. Zhu; S. H. Zhang; R. H. Zhang; Z. P. Du (International Journal of Remote Sensing, 2007)

Diversity and evolution of a newly emerged North American Type 1 porcine arterivirus: analysis of isolates collected between 1999 and 2004 - Y. Fang; P. Schneider; W. P. Zhang; K. S. Faaberg; E. A. Nelson; R. R. R. Rowland (Archives of Virology, 2007)

Genetic polymorphisms in the oxidative stress pathway and susceptibility to non-Hodgkin lymphoma - Qing Lan; Tongzhang Zheng; Min Shen; Yawei Zhang; Sophia S. Wang; Shelia H. Zahm; Theodore R. Holford; Brian Leaderer; Peter Boyle; Stephen Chanock (Human Genetics, 2007)

Cs-dominant polylithionite in the Koktokay#3 pegmatite, Altai, NW China: in situ micro-characterization and implication for the storage of radioactive cesium - R. C. Wang; H. Hu; A. C. Zhang; F. Fontan; Ph. de Parseval; S. Y. Jiang (Contributions to Mineralogy and Petrology, 2007)

A roni‐like virus associated with mortalities of the freshwater crab, Eriocheir sinensis Milne Edwards, cultured in China, exhibiting ‘sighs disease’ and black gill syndrome - S Zhang; J‐R Bonami (Journal of Fish Diseases, 2007)

Thiolated Chitosan/DNA Nanocomplexes Exhibit Enhanced and Sustained Gene Delivery - Dongwon Lee; Weidong Zhang; Shawna A. Shirley; Xiaoyuan Kong; Gary R. Hellermann; Richard F. Lockey; Shyam S. Mohapatra (Pharmaceutical Research, 2007)

Two new chemical constituents from Daphne odora Thunb. var. marginata - W. Zhang; W. D. Zhang; R. H. Liu; Y. H. Shen; C. Zhang; H. S. Cheng; P. Fu; L. Shan (Natural Product Research, 2006)

Identification of microsatellite markers linked to powdery mildew resistance gene Pm2 in wheat - Y. Qiu; X. Sun; R. Zhou; X. Kong; S. Zhang; J. Jia (Cereal Research Communications, 2006)

Two new xanthones from Hypericum japonicum - P. Fu; W.-D. Zhang; R. H. Liu; T.-Z. Li; Y.-H. Shen; H.-L. Li; W. Zhang; H.-S. Chen (Natural Product Research, 2006)

Effects of recombinant human growth hormone on acute lung injury in endotoxemic rats - C. Yi; S. R. Wang; S. Y. Zhang; S. J. Yu; C. X. Jiang; M. H. Zhi; Y. Huang (Inflammation Research, 2006)

Overall-effective measures for sustainable water resources management in the coastal areas of Shandong Province, China - Baoxiang Zhang; W. F. Geiger; S. Kaden; R. Kutzner; Zengliang Wang (Journal of Ocean University of China, 2006)

Polymorphisms in DNA repair genes and risk of non-Hodgkin lymphoma among women in Connecticut - Min Shen; Tongzhang Zheng; Qing Lan; Yawei Zhang; Shelia H. Zahm; Sophia S. Wang; Theodore R. Holford; Brian Leaderer; Meredith Yeager; Robert Welch; Daehee Kang; Peter Boyle; et al. (Human Genetics, 2006)

Bringing wild relatives back into the family: recovering genetic diversity in CIMMYT improved wheat germplasm - M. L. Warburton; J. Crossa; J. Franco; M. Kazi; R. Trethowan; S. Rajaram; W. Pfeiffer; P. Zhang; S. Dreisigacker; M. van Ginkel (Euphytica, 2006)

Model-Based Drug Development: The Road to Quantitative Pharmacology - Liping Zhang; Vikram Sinha; S. Thomas Forgue; Sophie Callies; Lan Ni; Richard Peck; Sandra R. B. Allerheiligen (Journal of Pharmacokinetics and Pharmacodynamics, 2006)

Construction of a quinoa (Chenopodium quinoa Willd.) BAC library and its use in identifying genes encoding seed storage proteins - M. R. Stevens; C. E. Coleman; S. E. Parkinson; P. J. Maughan; H.-B. Zhang; M. R. Balzotti; D. L. Kooyman; K. Arumuganathan; A. Bonifacio; D. J. Fairbanks; E. N. Jellen; J. J. Stevens (Theoretical and Applied Genetics, 2006)

Molecular mapping of stripe rust resistance gene YrCH42 in Chinese wheat cultivar Chuanmai 42 and its allelism with Yr24 and Yr26 - G. Q. Li; Z. F. Li; W. Y. Yang; Y. Zhang; Z. H. He; S. C. Xu; R. P. Singh; Y. Y. Qu; X. C. Xia (Theoretical and Applied Genetics, 2006)

A Polyketide Synthase Gene Required for Biosynthesis of the Aflatoxin-like Toxin, Dothistromin - Rosie E. Bradshaw; Hongping Jin; Branwen S. Morgan; Arne Schwelm; Olivia R. Teddy; Carolyn A. Young; Shuguang Zhang (Mycopathologia, 2006)

The Impact of Nitrogen Placement and Tillage on NO, N2O, CH4 and CO2 Fluxes from a Clay Loam Soil - Xuejun J. Liu; Arvin R. Mosier; Ardell D. Halvorson; Fusuo S. Zhang (Plant and Soil, 2006)

Soluble Organic Nitrogen Pools in Forest soils of Subtropical Australia - C. R. Chen; Z. H. Xu; S. L. Zhang; P. Keay (Plant and Soil, 2005)

Microsatellite mapping of a Triticum urartu Tum. derived powdery mildew resistance gene transferred to common wheat (Triticum aestivum L.) - Y. C. Qiu; R. H. Zhou; X. Y. Kong; S. S. Zhang; J. Z. Jia (Theoretical and Applied Genetics, 2005)

Forest biotechnology: Innovative methods, emerging opportunities - Narender S. Nehra; Michael R. Becwar; William H. Rottmann; Leslie Pearson; Kamal Chowdhury; Shujun Chang; H. Dayton Wilde; Robert J. Kodrzycki; Chunsheng Zhang; Katrina C. Gause; Dawn W. Parks; Maud A. Hinchee (In Vitro Cellular & Developmental Biology - Plant, 2005)

Tillage and Nitrogen Application Effects on Nitrous and Nitric Oxide Emissions from Irrigated Corn Fields - X. J. Liu; A. R. Mosier; A. D. Halvorson; F. S. Zhang (Plant and Soil, 2005)

Formulation of an ocean model for global climate simulations - S. M. Griffies; A. Gnanadesikan; K. W. Dixon; J. P. Dunne; R. Gerdes; M. J. Harrison; A. Rosati; J. L. Russell; B. L. Samuels; M. J. Spelman; M. Winton; R. Zhang (Ocean Science, 2005)
This paper summarizes the formulation of the ocean component to the Geophysical Fluid Dynamics Laboratory's (GFDL) climate model used for the 4th IPCC Assessment (AR4) of global climate change. In particular, it reviews the numerical schemes and physical parameterizations that make up an ocean climate model and how these schemes are pieced together for use in a state-of-the-art climate model. Features of the model described here include the following: (1) tripolar grid to resolve the Arctic Ocean without polar filtering, (2) partial bottom step representation of topography to better represent topographically influenced advective and wave processes, (3) more accurate equation of state, (4) three-dimensional flux limited tracer advection to reduce overshoots and undershoots, (5) incorporation of regional climatological variability in shortwave penetration, (6) neutral physics parameterization for representation of the pathways of tracer transport, (7) staggered time stepping for tracer conservation and numerical efficiency, (8) anisotropic horizontal viscosities for representation of equatorial currents, (9) parameterization of exchange with marginal seas, (10) incorporation of a free surface that accomodates a dynamic ice model and wave propagation, (11) transport of water across the ocean free surface to eliminate unphysical ``virtual tracer flux" methods, (12) parameterization of tidal mixing on continental shelves. We also present preliminary analyses of two particularly important sensitivities isolated during the development process, namely the details of how parameterized subgridscale eddies transport momentum and tracers.

Construction of two BAC libraries from cucumber (Cucumis sativus L.) and identification of clones linked to yield component quantitative trait loci - Y.-W. Nam; J.-R. Lee; K.-H. Song; M.-K. Lee; M. D. Robbins; S.-M. Chung; J. E. Staub; H.-B. Zhang (Theoretical and Applied Genetics, 2005)

Lyophilized Paclitaxel Magnetoliposomes as a Potential Drug Delivery System for Breast Carcinoma via Parenteral Administration: In Vitro and in Vivo Studies - J. Q. Zhang; Z. R. Zhang; H. Yang; Q. Y. Tan; S. R. Qin; X. L. Qiu (Pharmaceutical Research, 2005)

2. Histaminergic mechanisms in the CNS - G. B. Fox; T. A. Esbenshade; J. B. Pan; K. E. Browman; M. Zhang; M. E. Ballard; R. J. Radek; H. Miner; R. S. Bitner; K. M. Krueger; B. B. Yao; R. Faghih; et al. (Inflammation Research, 2005)

Evaluating a ‘Free Ion Activity Model’ applied to metal uptake by Lolium perenne L. grown in contaminated soils. - R. L. Hough; A. M. Tye; N. M. J. Crout; S. P. McGrath; H. Zhang; S. D. Young (Plant and Soil, 2005)

Molecular diagnosis of Fusobacterium necrophorum infection (Lemierre?s syndrome) - S. H. Aliyu; P. F. K. Yong; M. J. Newport; H. Zhang; R. K. Marriott; M. D. Curran; H. Ludlam (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Linking the northern hemisphere sea-ice reduction trend and the quasi-decadal arctic sea-ice oscillation - J Wang; M Ikeda; S Zhang; R Gerdes (Climate Dynamics, 2005)

Worker Exposure to Diazinon During Flea Control Operations in Response to a Plague Epizootic - A. C. Gerry; X. Zhang; T. Walker; S. Frederickson; M. Metzger; R. Hu; R. I. Krieger (Bulletin of Environmental Contamination and Toxicology, 2005)

Early gene response in lithium chloride induced apoptosis - W. V. Zhang; M. Jllig; A. R. Connolly; N. S. Stott (Apoptosis, 2005)

Pistil induction by hormones from callus of Oryza sativa in vitro - Y. R. An; X. G. Li; H. Y. Su; X. S. Zhang (Plant Cell Reports, 2004)

Photocatalytic Regeneration of Exhausted Activated Carbon Saturated with Phenol - S. X. Liu; C. L. Sun; S. R. Zhang (Bulletin of Environmental Contamination and Toxicology, 2004)

Towards automation of palynology 3: pollen pattern recognition using Gabor transforms and digital moments - Y. Zhang; D. W. Fountain; R. M. Hodgson; J. R. Flenley; S. Gunetileke (Journal of Quaternary Science, 2004)
The classification of pollen grains using texture information in combination with shape features is presented in this paper. The surface texture of pollen is characterised by using Gabor transforms, the geometric shape is described by using moment invariants, and the pollen grains are classified by an artificial neural network. In an experiment with five types of pollen grains, more than 97% of samples are correctly classified. Copyright © 2004 John Wiley & Sons, Ltd.

Purification and characterization of a new reovirus from the Chinese mitten crab, Eriocheir sinensis - S Zhang; Z Shi; J Zhang; J‐R Bonami (Journal of Fish Diseases, 2004)
A new reovirus was recently isolated from a freshwater crab, the Chinese mitten crab, Eriocheir sinensis , in China. The complete viral particles are 55 nm in diameter, icosahedral, non‐enveloped and have a mean buoyant density of 1.39 g cm −3 in CsCl gradient. The viral genome is composed of 12 pieces of dsRNA with an electrophoretic pattern of 3/4/2/3. This virus infects connective tissue of the gills, gut and hepatopancreas. Partial cDNA cloning and sequence analysis showed that the RNA‐dependent RNA polymerase is located in the first RNA segment. From its biochemical, ultrastructural and physicochemical properties, this virus is quite different from the genus Aquareovirus (Reoviridae). It may represent a new genus of Reoviridae, different from the other crab reoviruses, P and W 2 .

Time-dependent Interactions of Glibenclamide with CFTR: Kinetically Complex Block of Macroscopic Currents - Z.-R. Zhang; G. Cui; S. Zeltwanger; N.A. McCarty (The Journal of Membrane Biology, 2004)

Steady-State Interactions of Glibenclamide with CFTR: Evidence for Multiple Sites in the Pore - Z.-R. Zhang; S. Zeltwanger; N.A. McCarty (The Journal of Membrane Biology, 2004)

Residues of Hexachlorocyclohexane Isomers and Their Distribution Characteristics in Soils in the Tianjin Area, China - Z. M. Gong; F. L. Xu; R. Dawson; J. Cao; W. X. Liu; B. G. Li; W. R. Shen; W. J. Zhang; B. P. Qin; R. Sun; S. Tao (Archives of Environmental Contamination and Toxicology, 2004)

Localization of jointless-2 gene in the centromeric region of tomato chromosome 12 based on high resolution genetic and physical mapping - M. A. Budiman; S-B. Chang; S. Lee; T. J. Yang; H-B. Zhang; H. de Jong; R. A. Wing (Theoretical and Applied Genetics, 2004)

Application of a ?Big-Tree? model to regional climate modeling: a sensitivity study - X.-M. Zeng; M. Zhao; R.-C. Yu; N.-S. Lin; Y.-Q. Zheng; L.-J. Zhang; R.-J. Zhang (Theoretical and Applied Climatology, 2003)

Mapping QTLs and candidate genes for rice root traits under different water-supply conditions and comparative analysis across three populations - B. S. Zheng; L. Yang; W. P. Zhang; C. Z. Mao; Y. R. Wu; K. K. Yi; F. Y. Liu; P. Wu (Theoretical and Applied Genetics, 2003)

Snipping polymorphisms from large EST collections in barley (Hordeum vulgare L.) - R. Kota; S. Rudd; A. Facius; G. Kolesov; T. Thiel; H. Zhang; N. Stein; K. Mayer; A. Graner (Molecular Genetics and Genomics, 2003)

Interleukin-10 promoter polymorphisms and the outcome of hepatitis C virus infection - Susanne Knapp; Branwen J. W. Hennig; Angela J. Frodsham; Lyna Zhang; Simon Hellier; Mark Wright; Rob Goldin; Adrian V. S. Hill; Howard C. Thomas; Mark R. Thursz (Immunogenetics, 2003)

Extra small virus‐like particles (XSV) and nodavirus associated with whitish muscle disease in the giant freshwater prawn, Macrobrachium rosenbergii - D Qian; Z Shi; S Zhang; Z Cao; W Liu; L Li; Y Xie; I Cambournac; J‐R Bonami (Journal of Fish Diseases, 2003)
A disease of Macrobrachium rosenbergii , the giant freshwater prawn, farmed in China was recently recorded in Zhejiang, Jiangsu, Shanghai, Guangxi and Guangdong provinces. The clinical sign of the disease, which develops in post‐larvae (PL), is a whitish appearance of the muscles, particularly noticeable in the abdomen. Mortalities may reach 100% in some hatcheries. Investigations by transmission electron microscopy after negative staining of diseased PL homogenates showed the presence of two types of viral particles: one, unenveloped, icosahedral in shape, 26–27 nm in diameter, the second, much smaller, about 14–16 nm in diameter, designated extra small virus particle (XSV). The large virus has a genome with two pieces of ssRNA (RNA‐1 and RNA‐2), of 3 and 1.2 kb, respectively. Hybridization tests confirmed that this large virus is closely related to M. rosenbergii nodavirus ( Mr NV) which was isolated from diseased prawns in a hatchery in the French West Indies. Its very small size and hypothesized biochemical and biological characteristics suggest XSV is a new type of crustacean virus. As XSV has always been found associated with the larger virus (nodavirus) and is located in muscle and connective cells of diseased animals, it could be an autonomous virus, a helper‐type virus or a satellite‐like virus.

Time-domain Pure-state Polarization Analysis of Surface Waves Traversing California - J. Zhang; W. R. Walter; T. Lay; R.-S. Wu1 (Pure and Applied Geophysics, 2003)

Gene content and organization of an 85-kb DNA segment from the genome of the phytopathogenic mollicute Spiroplasma kunkelii - Y. Zhao; R. W. Hammond; R. Jomantiene; E. L. Dally; I.-M. Lee; H. Jia; H. Wu; S. Lin; P. Zhang; S. Kenton; F. Z. Najar; A. Hua; et al. (Molecular Genetics and Genomics, 2003)

Transformation of triploid bermudagrass (Cynodon dactylon x C. transvaalensis cv. TifEagle) by means of biolistic bombardment - G. Zhang; S. Lu; T. A. Chen; C. R. Funk; W. A. Meyer (Plant Cell Reports, 2003)

A novel assay for discovery and characterization of pro-apoptotic drugs and for monitoring apoptosis in patient sera - K. Bivén; H. Erdal; M. Hägg; T. Ueno; R. Zhou; M. Lynch; B. Rowley; J. Wood; C. Zhang; M. Toi; M. C. Shoshan; S. Linder (Apoptosis, 2003)

Cloning and analysis of the mating-type idiomorphs from the barley pathogen Septoria passerinii - S. B. Goodwin; C. Waalwijk; G. H. J. Kema; J. R. Cavaletto; G. Zhang (Molecular Genetics and Genomics, 2003)

Construction of a BAC library and generation of BAC end sequence-tagged connectors for genome sequencing of the African malaria mosquito Anopheles gambiae - Y. S. Hong; J. R. Hogan; X. Wang; A. Sarkar; C. Sim; B. J. Loftus; C. Ren; E. R. Huff; J. L. Carlile; K. Black; H.-B. Zhang; M. J. Gardner; et al. (Molecular Genetics and Genomics, 2003)

Characterization and Temporal Variation of Asian Dust Aerosol from a Site in the Northern Chinese Deserts - X. Y. Zhang; S. L. Gong; R. Arimoto; Z. X. Shen; F. M. Mei; D. Wang; Y. Cheng (Journal of Atmospheric Chemistry, 2003)

Subcellular targeting domains of Abutilon mosaic geminivirus movement protein BC1 - S. C. Zhang; R. Ghosh; H. Jeske (Archives of Virology, 2002)

Transformation of recalcitrant maize elite inbreds using in vitro shoot meristematic cultures induced from germinated seedlings - Zhang S.; Williams-Carrier R.; Lemaux P. (Plant Cell Reports, 2002)

Genetic and physical mapping of a rice blast resistance locus, Pi-CO39(t), that corresponds to the avirulence gene AVR1-CO39 of Magnaporthe grisea - R. Chauhan; M. Farman; H.-B. Zhang; S. Leong (Molecular Genetics and Genomics, 2002)

Phytoplankton iron limitation in the Humboldt Current and Peru Upwelling - D. A. Hutchins; C. E. Hare; R. S. Weaver; Y. Zhang; G. F. Firme; G. R. DiTullio; M. B. Alm; S. F. Riseman; J. M. Maucher; M. E. Geesey; C. G. Trick; G. J. Smith; et al. (Limnology and Oceanography, 2002)
We investigated phytoplankton Fe limitation using shipboard incubation experiments in the highߚnutrient South American eastern boundary current regime. Low ambient Fe concentrations (~0.1 nM) in water collected from the Humboldt and Peru Currents were supplemented with a range of added Fe levels up to 2.5 nM. Phytoplankton chlorophyll a, photosystem II photosynthetic efficiency, and nitrate and phosphate drawdown increased in proportion to the amount of Fe added. The Humboldt Current algal community after Fe additions included colonial and flagellated Phaeocystis globosa and large pennate diatoms, whereas the Peru Upwelling assemblage was dominated by coccolithophorids and small pennate diatoms. Apparent halfߚsaturation constants for growth of the two communities were 0.17 nM Fe (Humboldt Current) and 0.26 nM Fe (Peru Upwelling). Net molar dissolved Si(OH) 4 : NO 3 - drawdown ratios were low in both experiments (~0.2ߝ0.7), but net particulate silica to nitrogen production ratios were higher. Fe limitation decreased net NO 3 - :PO 4 3- utilization ratios in the Humboldt Current incubation to well below Redfield values. Phytoplankton community sinking rates were decreased by Fe additions in the Peru Upwelling, suggesting potential Fe effects on carbon export. Our results confirm that primary producers in the Peru Upwelling/Humboldt Current system can be limited by Fe, but the biological and biogeochemical consequences of Fe limitation differ from Feߚlimited California coastal upwelling waters that have been previously studied.

Determination of Toxicokinetic Parameters for Bioconcentration of Water-Soluble Fraction of Petroleum Hydrocarbon Associated with No. 0 Diesel in Changjiang Estuary and Jiaozhou Bay: Model Versus Mesocosm Experiments - X. Wang; J. Zhang; X. Shi; C. Zhu; Y. An; S. Jun; R. Li; M. Zhu; S. Chen (Archives of Environmental Contamination and Toxicology, 2002)

Dopamine thioethers: Formation in brain and neurotoxicity - Kathleen S. Montine; Kathrin R. Sidell; Jing Zhang; Thomas J. Montine (Neurotoxicity Research, 2002)

Ultrafast Flow Quantification With Segmented k-Space Magnetic Resonance Phase Velocity Mapping - Haosen Zhang; Sandra S. Halliburton; James R. Moore; Orlando P. Simonetti; Paulo R. Schvartzman; Richard D. White; George P. Chatzimavroudis (Annals of Biomedical Engineering, 2002)

Using simple environmental variables to estimate below‐ground productivity in grasslands - R. A. Gill; R. H. Kelly; W. J. Parton; K. A. Day; R. B. Jackson; J. A. Morgan; J. M. O. Scurlock; L. L. Tieszen; J. V. Castle; D. S. Ojima; X. S. Zhang (Global Ecology and Biogeography, 2002)
In many temperate and annual grasslands, above‐ground net primary productivity (NPP) can be estimated by measuring peak above‐ground biomass. Estimates of below‐ground net primary productivity and, consequently, total net primary productivity, are more difficult. We addressed one of the three main objectives of the Global Primary Productivity Data Initiative for grassland systems to develop simple models or algorithms to estimate missing components of total system NPP. Any estimate of below‐ground NPP (BNPP) requires an accounting of total root biomass, the percentage of living biomass and annual turnover of live roots. We derived a relationship using above‐ground peak biomass and mean annual temperature as predictors of below‐ground biomass ( r 2 = 0.54; P = 0.01). The percentage of live material was 0.6, based on published values. We used three different functions to describe root turnover: constant, a direct function of above‐ground biomass, or as a positive exponential relationship with mean annual temperature. We tested the various models against a large database of global grassland NPP and the constant turnover and direct function models were approximately equally descriptive ( r 2 = 0.31 and 0.37), while the exponential function had a stronger correlation with the measured values ( r 2 = 0.40) and had a better fit than the other two models at the productive end of the BNPP gradient. When applied to extensive data we assembled from two grassland sites with reliable estimates of total NPP, the direct function was most effective, especially at lower productivity sites. We provide some caveats for its use in systems that lie at the extremes of the grassland gradient and stress that there are large uncertainties associated with measured and modelled estimates of BNPP.

The bacterial cytosine deaminase gene used as a conditional negative selection marker in transgenic rice plants - S. Dai; R. Carcamo; Z. Zhang; S. Chen; R.N. Beachy (Plant Cell Reports, 2001)

Prostate Carcinoma Skeletal Metastases: Cross-talk between Tumor and Bone - Evan T. Keller; Jian Zhang; Carlton R. Cooper; Peter C. Smith; Laurie K. McCauley; Kenneth J. Pienta; Russell S. Taichman (Cancer and Metastasis Reviews, 2001)

Two genetic linkage maps of tetraploid roses - S. Rajapakse; D. H. Byrne; L. Zhang; N. Anderson; K. Arumuganathan; R. E. Ballard (Theoretical and Applied Genetics, 2001)

Carbon mitigation potential and costs of forestry options in Brazil, China, India, Indonesia, Mexico, the Philippines and Tanzania - J.A. Sathaye; W.R. Makundi; K. Andrasko; R. Boer; N.H. Ravindranath; P. Sudha; S. Rao; R. Lasco; F. Pulhin; O. Masera; A. Ceron; J. Ordonez; et al. (Mitigation and Adaptation Strategies for Global Change, 2001)

Identification of genome constitution of Oryza malampuzhaensis, O. minuta,and O. punctata by multicolor genomic in situ hybridization - C.-B. Li; D.-M. Zhang; S. Ge; B.-R. Lu; D.-Y. Hong (Theoretical and Applied Genetics, 2001)

Differentiation and inter-genomic relationships among C, E and D genomes in the Oryzaofficinalis complex (Poaceae) as revealed by multicolor genomic in situ hybridization - C.-B. Li; D.-M. Zhang; S. Ge; B.-R. Lu; D.-Y. Hong (Theoretical and Applied Genetics, 2001)

High-resolution structural analysis of biolistic transgene integration into the genome of wheat - S. A. Jackson; P. Zhang; W. P. Chen; R. L. Phillips; B. Friebe; S. Muthukrishnan; B. S. Gill (Theoretical and Applied Genetics, 2001)

Locating genomic regions associated with components of drought resistance in rice: comparative mapping within and across species - J. Zhang; H. G. Zheng; A. Aarti; G. Pantuwan; T. T. Nguyen; J. N. Tripathy; A. K. Sarial; S. Robin; R. C. Babu; Bay D. Nguyen; S. Sarkarung; A. Blum; et al. (Theoretical and Applied Genetics, 2001)

Contributions of genetic drift and negative selection on the evolution of three strains of wheat streak mosaic tritimovirus - I.-R. Choi; J. S. Hall; M. Henry; L. Zhang; G. L. Hein; R. French; D. C. Stenger (Archives of Virology, 2001)

Observational Evidence of Recent Change in the Northern High-Latitude Environment - M. C. Serreze; J. E. Walsh; F. S. Chapin; T. Osterkamp; M. Dyurgerov; V. Romanovsky; W. C. Oechel; J. Morison; T. Zhang; R. G. Barry (Climatic Change, 2000)

Direct Comparison of NPPB and DPC as Probes of CFTR Expressed in Xenopus Oocytes - Z.-R. Zhang; S. Zeltwanger; N.A. McCarty (The Journal of Membrane Biology, 2000)

Production of transgenic maize from bombarded type II callus: Effect of gold particle size and callus morphology on transformation efficiency - Bronwyn R. Frame; Hongyi Zhang; Suzy M. Cocciolone; Lyudmila V. Sidorenko; Charles R. Dietrich; Sue Ellen Pegg; Shifu Zhen; Patrick S. Schnable; Kan Wang (In Vitro Cellular & Developmental Biology - Plant, 2000)

Abstracts of presentations on selected topics at the XIVth international plant protection congress (IPPC) July 25–30, 1999 - R. Hull; H. A. Kuiper; Maryvon Y. Noordam; Marjorie A. Hoy; Jenny S. Cory; A. C. Fereres; P. Gonzalez; F. Meins; Y. Elkind; Benedicte Charrier; P. Meyer; M. Metzlaff; et al. (Phytoparasitica, 1999)

Selenium-dependent glutathione peroxidase modules encoded by RNA viruses - W. Zhang; C. S. Ramanathan; R. G. Nadimpalli; A. A. Bhat; A. G. Cox; E. W. Taylor (Biological Trace Element Research, 1999)

Genetic transformation of commercial cultivars of oat ( Avena sativa L.) and barley ( Hordeum vulgare L.) using in vitro shoot meristematic cultures derived from germinated seedlings - S. Zhang; M.-J. Cho; T. Koprek; R. Yun; P. Bregitzer; P. G. Lemaux (Plant Cell Reports, 1999)

Mutation in the leptin receptor (Lepr fa ) causes fat-storage-independent hyperleptinaemia in neonatal rats - C. Hufnagel; S. Eiden; B. Nuesslein-Hildesheim; Y. Zhang; R. Leibel; I. Schmidt (Pflügers Archiv - European Journal of Physiology, 1999)

Mutation in the leptin receptor ( Lepr fa ) causes fat-storage-independent hyperleptinaemia in neonatal rats - C. Hufnagel; S. Eiden; B. Nuesslein-Hildesheim; Y. Zhang; R. Leibel; I. Schmidt (Pflügers Archiv - European Journal of Physiology, 1999)

Production of transgenic tropical maize with cryIAb and cryIAc genes via microprojectile bombardment of immature embryos - N. Bohorova; W. Zhang; P. Julstrum; S. McLean; B. Luna; R. M. Brito; L. Diaz; M. E. Ramos; P. Estanol; M. Pacheco; M. Salgado; D. Hoisington (Theoretical and Applied Genetics, 1999)

A new human prostate carcinoma cell line, 22Rv1 - R. Michael Sramkoski; Thomas G. Pretlow; Joseph M. Giaconia; Theresa P. Pretlow; Stuart Schwartz; Man-Sun Sy; Susan R. Marengo; Johng S. Rhim; Desheng Zhang; James W. Jacobberger (In Vitro Cellular & Developmental Biology - Animal, 1999)

Differentiation of bermudagrass (Cynodon spp.) genotypes by AFLP analyses - L.-H. Zhang; P. Ozias-Akins; G. Kochert; S. Kresovich; R. Dean; W. Hanna (Theoretical and Applied Genetics, 1999)

Predicting movement during anaesthesia by complexity analysis of electroencephalograms - X. -S. Zhang; R. J. Roy (Medical & Biological Engineering & Computing, 1999)

Limitations to tobacco mosaic virus infection of turnip - Y. Zhang; R. T. Lartey; S. D. Hartson; T. C. Voss; U. Melcher (Archives of Virology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

A protocol for consistent, large-scale production of fertile transgenic rice plants - L. Chen; S. Zhang; R. N. Beachy; C. M. Fauquet (Plant Cell Reports, 1998)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Petrogenesis of impure dolomitic marble from the Dabie Mountains, central China - S. Omori; J. G. Liou; R. Y. Zhang; Y. Ogasawara (Island Arc, 1998)
Petrogeneses of impure dolomitic marble and enclosed eclogite from the Xinyan area, Dabie ultrahigh‐pressure (UHP) metamorphic terrane, central China were investigated with a special focus on fluid characteristics. Identified carbonate‐bearing UHP assemblages are Dol + Coe ± Arg (or Mgs) ± Ap, Dol + Omp ± Coe ± Ap ± Arg (or Mgs), Phen + Omp + Coe + Dol ± Arg and Dol + Coe + Phen + Rt ± Omp ± Arg ± Ap. Retrograde assemblages are characterized by symplectitic replacement of Tr–Ab and Di–Ab after omphacite, and Phl–Pl symplectite after phengite. The P–T conditions of UHP metamorphism were estimated to be P > 2.7 GPa and T > 670 °C by the occurrence of coesite inclusions in garnet in enclosed eclogite and garnet–clinopyroxene geothermometer. The P–T conditions of initial amphibolitization were estimated to be 620 X CO 2 space in the systems NaAl–CMSCH and KCMASCH were calculated in order to constrain fluid compositions. Compositions and parageneses of UHP‐stage minerals suggest the presence of fluid in UHP and exhumation stages. Occurrence of retrograde low‐variance assemblages indicates that fluid composition during amphibolitization was buffered. A metastable persistence of magnesite and very restricted occurrence of calcite, magnesite and dolomite suggest a low fluid content in the post‐amphibolitization stage.

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Caspase inhibition prevents staurosporine-induced apoptosis in CHO-K1 cells - G. Zhang; G. Yan; V. Gurtu; C. Spencer; S. R. Kain (Apoptosis, 1998)

East Asian winter monsoon: results from eight AMIP models - Y. Zhang; K. R. Sperber; J. S. Boyle; M. Dix; L. Ferranti; A. Kitoh; K. M. Lau; K. Miyakoda; D. Randall; L. Takacs; R. Wetherald (Climate Dynamics, 1997)

Linkage disequilibrium studies in multiple endocrine neoplasia type 1 (MEN1) - J. H. D. Bassett; A. A. J. Pannett; S. A. Forbes; R. V. Thakker; M. McCarthy; A. P. Read; B. T. Teh; C. Larsson; S. Kytl; J. Leisti; P. Salmela; G. Weber; et al. (Human Genetics, 1997)

Variation in coat protein genes among five geographicallydifferent isolates of rice tungro spherical virus - S. Zhang; G. Lee; J. W. Davies; R. Hull (Archives of Virology, 1997)

Mapping of the gene encoding the B56β subunit of protein phosphatase 2A (PPP2R5B) to a 0.5-Mb region of chromosome 11q13 and its exclusion as a candidate gene for multiple endocrine neoplasia type 1 (MEN1) - S. A. Forbes; A. A. J. Pannett; J. H. D. Bassett; B. Harding; C. Wooding; R. V. Thakker; R. Butler; D. Ogilvie; R. Anand; P. Gaudray; G. Weber; C. Larsson; et al. (Human Genetics, 1997)

Pyramiding of bacterial blight resistance genes in rice: marker-assisted selection using RFLP and PCR - N. Huang; E. R. Angeles; J. Domingo; G. Magpantay; S. Singh; G. Zhang; N. Kumaravadivel; J. Bennett; G. S. Khush (Theoretical and Applied Genetics, 1997)

High-resolution mapping of the spm (niemann-pick type C) locus on mouse chromosome 18 - R. P. Erickson; R. A. Aviles; J. Zhang; M. A. Kozloski; W. S. Garver; R. A. Heidenreich (Mammalian Genome, 1997)

Cosmid-derived markers anchoring the bovine genetic map to the physical map - L. Ferretti; B. G. D. Urquhart; A. Eggen; I. Olsaker; B. Harlizius; B. Castiglioni; A. Mezzelani; S. Solinas Toldo; U. Thieven; Y. Zhang; A. L. G. Morgan; V. M. Teres; et al. (Mammalian Genome, 1997)

Influenza infection in humans and pigs in southeastern China - N. Zhou; S. He; T. Zhang; W. Zou; L. Shu; G. B. Sharp; R. G. Webster (Archives of Virology, 1996)

Description of an XRF system for multielemental analysis - L. Wielopolski; R. Zhang; S. H. Cohn (Biological Trace Element Research, 1987)

Determination of ruthenium on DNA by XRF - L. Wielopolski; R. Zhang; M. J. Clarke; S. H. Cohn (Biological Trace Element Research, 1987)